Method for preparing supported precious metal-metal alloy composites and resulting supported precious metal-metal alloy composites
The double passivation GD synthesis method addresses the challenges of existing electrocatalyst preparation by forming passivated oxide layers and using adsorbed gases to control nanoparticle growth, resulting in highly dispersed noble metal nanoparticles with enhanced catalytic activity and reduced Pt usage for PEMFCs.
Patent Information
- Application Number
- JP2022504330
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-18
- Filing Date
- 2020-03-17
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-17
AI Technical Summary
Existing methods for preparing electrocatalysts for proton exchange membrane fuel cells (PEMFCs) face challenges such as high overpotentials in cathodic oxygen reduction reactions, high Pt loadings, high costs, and morphological instability due to complex synthesis processes like polyol-type synthesis, which are difficult to scale and require expensive materials and additional steps.
A double passivation galvanic displacement (GD) synthesis method involving the formation of a passivating oxide layer on less noble metal particles and using an adsorbed gas to cap noble metal nanoparticles, allowing for the precipitation of noble metal nanoparticles and alloys on a conductive support, preventing direct precipitation on the less noble metal and controlling particle growth.
The method produces highly dispersed, well-defined noble metal and alloy nanoparticles on a support, enhancing catalytic activity and reducing Pt usage, with improved stability and scalability, suitable for use in PEMFCs and other electrochemical energy conversion devices.
Smart Images

Figure 0007601853000005 
Figure 0007601853000006 
Figure 0007601853000007
Abstract
Description
[Technical field]
[0001] The present application relates to a method for the preparation of supported precious metal-metal alloy composites by a galvanic replacement synthesis process, and to the supported precious metal-metal alloy composites obtained by said process. In particular, the present application relates to a synthesis method for producing high performance supported precious metal-M alloy electrocatalyst composites, the supported precious metal-M alloy electrocatalyst composites obtained by said process, and their uses. [Background technology]
[0002] Proton exchange membrane fuel cells (PEMFCs), capable of efficiently converting hydrogen into electrical energy with only water (and heat) as by-products, will play a key role in future sustainable energy solutions. Before being widely adopted in large-scale industries, including the automotive sector, PEMFC technology must first address many intrinsic issues associated with electrocatalysis, such as the high overpotential of the cathodic oxygen reduction reaction (ORR), which requires high Pt loading, which in turn translates into high costs. This issue can be addressed by alloying Pt with less noble transition metals (e.g., Cu, Ni, or Co), which increase the intrinsic activity of the ORR and at the same time reduce the amount of Pt used.
[0003] In recent years, record ORR activities for Pt-based electrocatalysts have been reported annually. In many cases, these activities are well within the proposed performance targets for 2020 (0.44 A mg at 0.9 V). Pt; U.S. Department of Energy target) by a large margin. However, it should be noted here that their high activity is only achieved with thin film rotating disk electrodes (TF-RDE). Thus, none of the "record" activities have been transferred to "record" real PEMFC performance. One of the main reasons for this problem could be that their preparation methods are based on polyol-type synthesis. While this type of synthesis allows precise control of nanoparticle shape (i.e., allowing the creation of octahedral nanoparticles, nanoframes, nanowires, etc. with controlled shapes), it has several inherent limitations, such as (i) limited to the milligram-scale range per batch; (ii) long synthesis times; (iii) high temperatures and / or pressures (e.g., solvothermal synthesis); (iv) high cost of the acetylacetonate Pt precursor; (v) use of expensive and complex organic solvents and surfactants that need to be removed via additional synthesis steps; (vi) sequential synthesis of nanoparticles and their subsequent deposition onto support materials; and (vii) any thermal annealing process may cause undesirable morphological changes at already mild temperatures, resulting in the loss of desirable nanocrystalline faces. Similar morphological instability was observed at cathode conditions relevant for PEMFCs.
[0004] An alternative method for synthesizing supported Pt-based nanoparticles for use in PEMFCs is the so-called galvanic displacement (GD) or metal exchange, which is disclosed in US Patent Application 2012 / 0208108. It is generally recognized that in the case of GD-type synthesis, the cations of the more noble metal spontaneously exchange with the less noble sacrificial metal on the surface of the sacrificial metal itself. For this to happen, the less noble sacrificial metal is in the metallic state. Moreover, in order to achieve or rather maintain a nanoparticle morphology after the GD reaction step, the less noble sacrificial metal needs to already be in the form of highly dispersed nanoparticles before the GD step of the synthesis. This makes GD-type synthesis methods, like polyol-type synthesis, somewhat difficult to scale to industrially relevant levels.
[0005] Thus, there is a need for a simpler and more economically favorable process for the preparation of electrocatalytic materials containing precious metals compared to the methods of the prior art.It is therefore an object of the present invention to provide a method for the preparation of supported precious metal-alloy nanoparticle composite electrocatalysts that alleviates at least some of the limitations of the prior art. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] U.S. Patent Application No. 2012 / 0208108 Summary of the Invention
[0007] The objectives of the present invention are realized by a novel approach towards galvanic displacement (GD) reaction synthesis via a double passivation method.
[0008] In a first aspect, the present invention relates to a method for forming supported precious metal and / or precious metal-M alloy nanoparticle composites, where M is a less noble metal that has been galvanically displaced (GD) to precipitate the precious metal, the method comprising the steps of: (a) providing an M / S precursor material having metal M particles on electrically conductive support particles, where M is one or more metals having a lower standard electrode potential than noble metals; (b) suspending the M / S precursor material in a liquid medium having a pH at least such that an in situ passivating oxide is thermodynamically formed on the surfaces of metal M particles exposed to the liquid medium, thereby forming a passivated MO y forming a M / S suspension, where y is greater than 0 and up to the stoichiometric M oxide value; (c) the passivated MO y supplying, to the / S suspension, an adsorption gas capable of selectively adsorbing the precious metal to be precipitated; (d) the passivated MO yadding a precious metal precursor to the M / S suspension, thereby precipitating crystalline precious metal nanoparticles and / or crystalline precious metal-M alloy nanoparticles as a reaction product on the support particles by a galvanic replacement reaction; and (e) isolating and washing the as-synthesized reaction products.
[0009] The method according to the invention is a double passivation GD method. The first passivation involves the spontaneous growth of a passivating oxide layer on the exposed surface metal particles M on the support particles S. Without wishing to be bound by theory, the technical effect of the passivating oxide layer is to reduce the electronic conductivity between the liquid medium (e.g., aqueous phase) and the less noble sacrificial metal M, while increasing the electronic conductivity between the liquid medium and the MO. y The purpose of the passivated MO is to maintain ionic conductivity between the particles. y Upon introduction of the noble metal precursor into the / S suspension, the GD reaction between the noble metal precursor and the oxide-passivated metal M is initiated. The passivation of the less noble metal substantially blocks the direct deposition of the noble metal cations onto the less noble sacrificial metal M, while this results in favorable transport of electrons through the electrically conductive support particles. Thus, direct deposition of the noble metal onto the sacrificial metal M is avoided, and instead the GD reaction occurs via the electrically conductive support particles, so that dispersed noble metal nanoparticles and / or noble metal-M alloy nanoparticles are deposited onto the support particles. The second passivation involves providing an adsorbent gas that can be selectively adsorbed onto the surface of the noble metal. The technical effect of the second passivation is to shield (capping) the noble metal nanoparticles and / or noble metal-M alloy nanoparticles formed in the initial stage. This prevents excessive particle growth and promotes the formation of new noble metal nanoparticles and / or noble metal-M alloy nanoparticles at new sites on the support particles. Therefore, the as-synthesized nanoparticles produced by the present double passivation GD method are not core-shell type particles (e.g., those produced according to commonly known GD methods in which noble metal cations spontaneously exchange with less noble sacrificial metals on the surface of the sacrificial metal).
[0010] In one embodiment, the metal M of the M / S precursor in step (a) has its surface at least partially oxidized to form an ex situ passivated M+MO / S precursor.
[0011] In one embodiment, the liquid medium is water, preferably purified water.
[0012] In one embodiment, the liquid medium is a compound represented by the general formula C having 1 to 7 carbon atoms. n H 2n+1 Alcohols with OH, preferably C 1 ~C 3 The solvent is preferably an alcohol, or a mixture thereof, or an aqueous solution of said alcohol.
[0013] In certain embodiments, the pH of the liquid medium is adjusted before, during, and / or after suspension of the M / S precursor material and / or the at least partially ex situ passivated M+MO / S precursor.
[0014] In one embodiment, the passivated MO y The / S suspension is saturated with the adsorbate gas prior to the addition of the precious metal precursor.
[0015] In one embodiment, the adsorbed gas is MO from an external source. y / S suspension is added.
[0016] In one embodiment, the liquid has the general formula C n H 2n+1 Alcohols with OH, preferably C 1 ~C 3 The adsorbed gas may be at least partially formed in situ in suspension, or an alcohol, or a mixture thereof, or an aqueous solution of said alcohol.
[0017] In one embodiment, the addition of the adsorption gas is continued throughout the addition of the precious metal precursor.
[0018] In one embodiment, the precious metal precursor is a salt or the corresponding acid of the salt that is soluble in the liquid medium.
[0019] In one embodiment, the noble metal precursor is a halide salt of a noble metal (NM n+ Y n ) (including both hydrates and anhydrates), alkali metal halide salts (A m NM n+ Y m+n ) (both hydrated and anhydrous), or the corresponding hydrohalic acids (H m NM n+ Y m+n ), where NM=noble metal; m=typically 1 or 2, n=typically 1, 2, 3 or 4, and X=alkali metal cation Li + , Na + , K + ;Y=halide F - , Cl - , Br - , I - It is.
[0020] In some embodiments, the noble metal is Pt, Ir, Rh, Pd, or Au.
[0021] In one embodiment, the adsorbed gas is carbon monoxide (CO), hydrogen (H 2 ), methanethiol (MeHS), or hydrogen sulfide (H 2 S).
[0022] In one embodiment, the precious metal is Pt or Pd and the adsorbed gas is CO.
[0023] In one embodiment, the noble metal is Pd and the adsorbed gas is hydrogen gas.
[0024] In some embodiments, the less noble metal, M, is selected from Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Mo, W, Zn, Y, Gd, Pd, or mixtures thereof.
[0025] In some embodiments, the less noble metal, M, is selected from Cu, Ni, Co, Fe, Ag, Mo, W, Zn, Cr, Pb, Ti, or mixtures thereof.
[0026] In some embodiments, the less noble metal, M, is selected from Cu, Ni, Co, or mixtures thereof.
[0027] In one embodiment, the support material is an electrically conductive material that is more electrically conductive (conductive) than the conductivity of the passivated M oxide formed, and is selected from a carbon material, a ceramic material, or a composite material.
[0028] In one embodiment, the carbon material is an electrically conductive carbon particle selected from carbon black, carbon nanotubes (CNTs), graphite or graphene, or derivatives thereof.
[0029] In one embodiment, the ceramic material is antimony tin oxide (ATO), fluorine doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x N y ) are electrically conductive ceramic particles selected from the group consisting of:
[0030] In one embodiment, the washing in step (e) comprises redispersing the as-synthesized reaction product in a fresh liquid medium and filtering at least once.
[0031] In one embodiment, the washed and filtered as-synthesized reaction product is dried.
[0032] In certain embodiments, the method further comprises a step (f) of thermal annealing the as-synthesized product.
[0033] In one embodiment, the thermal annealing step (f) is carried out at a temperature between 450 and 1200° C. in an inert, oxygen-free, and / or reducing atmosphere.
[0034] In a second aspect, the present invention provides a method for preparing a MOS substrate on a support material S. y (y is greater than 0 and up to the stoichiometric M oxide value), where M is a less noble metal galvanically replaced by the noble metal in cationic state, said composite material being an as-synthesized reaction product obtainable by the method of any of the embodiments according to the first aspect of the present invention excluding the thermal annealing step f), said composite material comprising highly dispersed noble metal and / or noble metal-M nanoparticles on a support material.
[0035] In a third aspect, the present invention relates to a composite material comprising precious metal nanoparticles and / or precious metal-M alloy nanoparticles on a support material S, where M is a less noble metal galvanically substituted by a precious metal in cationic state, the composite material being obtainable by the method of any of the embodiments according to the first aspect of the invention comprising a thermal annealing step f), and comprising highly dispersed precious metal nanoparticles and / or precious metal-M nanoparticles on the support material.
[0036] In an embodiment of the invention according to the second or third aspect, the noble metal is Pt, Ir, Rh, Pd or Au.
[0037] In an embodiment of the invention according to the second or third aspect, the less noble metal M is Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Mo, W, Zn, Y, Gd, Pd, or mixtures thereof.
[0038] In an embodiment of the invention according to the second or third aspect, the less noble metal M is selected from Cu, Ni, Co, Fe, Ag, Mo, W, Zn, Cr, Pb, Ti, or mixtures thereof.
[0039] In an embodiment of the invention according to the second or third aspect, the less noble metal M is selected from Cu, Ni, Co or mixtures thereof.
[0040] In an embodiment of the invention according to the second or third aspect, the support material is an electrically conductive material selected from a carbon material, a ceramic material, or a composite material.
[0041] In an embodiment of the invention according to the second or third aspect, the carbon material is an electrically conductive carbon particle selected from carbon black, carbon nanotubes (CNT), graphite or graphene, or derivatives thereof.
[0042] In an embodiment of the invention according to the second or third aspect, the ceramic material is antimony tin oxide (ATO), fluorine doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x N y ) are electrically conductive ceramic particles selected from the group consisting of:
[0043] In an embodiment of the invention according to the second or third aspect, the precious metal is Pt, M is one or more of Cu, Ni or Co and the support material is carbon black.
[0044] In a fourth aspect, the present invention relates to the use of the composite material according to any one of the embodiments according to the second aspect of the present invention as an electrocatalyst in an electrochemical energy conversion device.
[0045] In a fifth aspect, the present invention relates to the use of the composite material according to any one of the embodiments according to the third aspect of the present invention as an electrocatalyst in an electrochemical energy conversion device.
[0046] In an embodiment of the use of the composite material, the electrocatalyst is a carbon supported Pt-M alloy nanoparticle electrocatalyst in a PEM fuel cell.
[0047] The present invention will become apparent from the detailed description given below. The detailed description and specific examples disclose preferred embodiments of the present invention by way of example only. Those skilled in the art will understand that, from the guidance of the detailed description, changes and modifications may be made within the scope of the present invention as defined in the appended claims.
[0048] Therefore, it should be understood that the description of the invention disclosed herein is not limited to the particular described steps of such methods, as modifications may be made to such methods. It should also be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting. It should be noted that, as used in the specification and the appended claims, the articles "a," "an," "the," and "said" are intended to mean that one or more elements are present, unless the context clearly dictates otherwise. Furthermore, the terms "comprising," "including," "containing," and similar terms do not exclude other elements or steps. [The present invention 1001] A method for forming supported precious metal nanoparticles and / or precious metal-M alloy nanoparticle composites, wherein M is a less noble metal that is galvanically substituted to precipitate the precious metal, the method comprising: (a) providing an M / S precursor material having metal particles M on electrically conductive support particles S, where M is one or more metals having a lower standard electrode potential than the noble metal; (b) suspending the M / S precursor material in a liquid medium and forming a passivated MO y forming a liquid medium having a pH at which an in situ passivating oxide is thermodynamically formed at least on surfaces of the metal M particles exposed to the liquid medium, and y is greater than 0 and up to the stoichiometric M oxide value; (c) introducing an adsorption gas capable of selectively adsorbing the precious metal to be deposited into the MO y 2. Supplying the mixture to a / S suspension; (d) The MO y adding a precious metal precursor to the M / S suspension, thereby precipitating crystalline precious metal nanoparticles and / or crystalline precious metal-M alloy nanoparticles as a reaction product on the support particles by a galvanic replacement reaction; and (e) separating and washing the as-synthesized reaction product. A method comprising: [The present invention 1002] 1001. The method of claim 1001, wherein in step (a) the metal M of said M / S precursor is at least partially oxidized to form an ex situ passivated M+MO / S precursor. [The present invention 1003] The liquid medium is selected from the group consisting of water, alcohol having 1 to 7 carbon atoms, CH 4 O~C 7 H 16 0, or a mixture thereof, or an aqueous solution of said alcohol. [The present invention 1004] The method of any of claims 1001 to 1003, wherein the pH of the liquid medium is adjusted before, during, and / or after suspension of the M / S precursor material and / or the at least partially ex-situ passivated M+MO / S precursor. [The present invention 1005] The passivated metal y The method of any of claims 1001 to 1004, wherein the / S suspension is saturated with said adsorption gas prior to addition of said precious metal precursor. [The present invention 1006] The method of any one of claims 10 to 5, wherein said adsorbed gas is provided from an external source and / or is formed at least partially in situ in said suspension. [The present invention 1007] The process of any one of claims 1005 to 1006, wherein the addition of said adsorption gas is continued during the addition of said precious metal precursor. [The present invention 1008] The method according to any one of claims 1001 to 1007, wherein said precious metal precursor is a salt soluble in said liquid medium or a corresponding acid of said salt. [The present invention 1009] The method according to any one of claims 1001 to 1008, wherein the noble metal is Pt, Ir, Rh, Pd, or Au. [The present invention 1010] The adsorbed gas is carbon monoxide (CO), hydrogen (H 2 ), methanethiol (MeHS), or hydrogen sulfide (H 2 Any of the methods of 1001 to 1009 of the present invention, selected from the following: [The present invention 1011] The method according to any one of claims 1001 to 1010, wherein the noble metal is Pt or Pd, and the adsorbed gas is CO. [The present invention 1012] The noble metal is Pd and the adsorption gas is H 2 The method according to any one of claims 1001 to 1010, [The present invention 1013] The process according to any one of claims 1001 to 1012, wherein said less noble metal M is selected from Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Sn, Mo, W, Zn, Y, Gd, Pd, or mixtures thereof. [The present invention 1014] The method according to any one of claims 1001 to 1013, wherein the support material is an electrically conductive material selected from a carbon material, a ceramic material, or a composite material, and has an electrical conductivity greater than the electrical conductivity of the passivated M oxide formed. [The present invention 1015] The method of claim 1014, wherein the carbon material is a conductive carbon particle selected from carbon black, carbon nanotubes (CNTs), graphite or graphene, or a derivative thereof. [The present invention 1016] The ceramic material is antimony tin oxide (ATO), fluorine doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x N y The method of the present invention 1014, wherein the ceramic particles are selected from the group consisting of: [The present invention 1017] The process of any of claims 1001 to 1016, wherein the washing in step (e) comprises redispersing said as-synthesized reaction product in a fresh liquid medium and filtering at least once. [The present invention 1018] The process of claim 1017, wherein said washed and filtered as-synthesized reaction product is dried. [The present invention 1019] The method of any of claims 1001 to 1018, further comprising a step (f) of thermal annealing said as-synthesized product. [The present invention 1020] 1019. A method according to claim 1019, wherein said thermal annealing step (f) is carried out at a temperature between 450 and 1200° C. under an inert, oxygen-free and / or reducing atmosphere. [The present invention 1021] MO oxide on a support material, y being greater than 0 and up to the stoichiometric M oxide value. y 10. A composite material comprising precious metal and / or precious metal-M alloy nanoparticles in combination with M, where M is a less noble metal galvanically substituted by said precious metal in cationic state, said composite material being obtainable by the process of inventions 1001-1018, said composite material being an as-synthesized reaction product comprising highly dispersed precious metal nanoparticles and / or precious metal-M nanoparticles on said support material. [The present invention 1022] A composite material comprising precious metal nanoparticles and / or precious metal-M alloy nanoparticles on a support material, where M is a less noble metal galvanically substituted by said precious metal in cationic state, said composite material being obtainable by the method of inventions 1001-1020, said composite material being an annealed reaction product comprising highly dispersed precious metal nanoparticles and / or precious metal-M nanoparticles on said support material. [The present invention 1023] The composite material of the present invention 1021 or 1022, wherein the precious metal is Pt, Ir, Rh, Pd, or Au. [The present invention 1024] The composite material of any one of claims 1021 to 1023, wherein the less noble metal M is Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Sn, Mo, W, Zn, Y, Gd, Pd, or a mixture thereof. [The present invention 1025] The composite material of any one of claims 1021 to 1024, wherein the support material is a conductive material selected from a carbon material, a ceramic material, or a composite material. [The present invention 1026] The composite material of the present invention, wherein the carbon material is a conductive carbon particle selected from carbon black, carbon nanotubes (CNTs), graphite or graphene, or a derivative thereof. [The present invention 1027] The ceramic material is antimony tin oxide (ATO), fluorine doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x N y The composite material of the present invention 1025, wherein the ceramic particles are selected from the following: [The present invention 1028] The composite material of claim 1021 or 1022, wherein the precious metal is Pt, the M is one or more of Cu, Ni, or Co, and the support material is carbon black. [The present invention 1029] Use of any of the composite materials according to the present invention Nos. 1021 to 1028 as an electrode catalyst in an electrochemical energy conversion device. [The present invention 1030] 1029. Use of a composite material according to the present invention, wherein said composite material has been treated by a catalytic activation treatment. [The present invention 1031] 1030. Use of the composite material of claim 1029 or 1030, wherein said catalyst is a carbon-supported Pt-M alloy nanoparticle electrocatalyst in a PEM fuel cell. [Brief description of the drawings]
[0049] [Figure 1] 1 shows a double passivation step in the GD synthesis method of the present invention. [Diagram 2] Measurements of Example 2 (however, they are schematic depictions of the process); a)-c) TEM analysis; d) XRD analysis of the main synthesis steps to produce PtCu3 / C (GD synthesis in the presence of CO); e) Size distribution of PtCu nanoparticles from PtCu+CuO / C composite before thermal annealing and PtCu3 / C after thermal annealing (GD synthesis in the presence of CO). [Diagram 3] a) Results of Tests 1 and 2, for the in situ formation of a passivating Cu oxide layer on a Cu precursor on a carbon support. b) Results of Tests 3 and 4, for the in situ formation of a passivating Co oxide layer on a Co precursor on a carbon support. [Figure 4]XRD of various PtCu3 / C electrocatalysts (Examples 1, 2, 4, 8) with similar Pt:Cu chemical composition show differences in total metal loading (Pt+Cu) by using Cu / C precursors with different Cu loadings on the same carbon support. [Diagram 5] CO stripping CV (0.1 M HClO4, Ar saturated, no rotation, 20 mV / s), ORR polarization curves (0.1 M HClO4, O2 saturated, ohmic resistance compensated, background current subtracted, 1600 rpm, 20 mV / s) and calculated Tafel plots of PtCu3 / C electrocatalysts (Examples 1, 2, 4, 8) after 200 cycles of in situ EA (0.05-1.2 V vs. RHE, 300 mV / s). SA and MA as well as ECSACO measured at 0.9 V vs. RHE are available in Table 1. [Figure 6] XRD of various Pt-Cu / C electrocatalysts (Examples 4-7) show differences in Pt:Cu chemical composition when different amounts of Pt precursor are added to the same Cu / C precursor. [Figure 7] CO stripping CV (0.1 M HClO4, Ar saturated, no rotation, 20 mV / s), ORR polarization curves (0.1 M HClO4, O2 saturated, ohmic resistance compensation, background current subtraction, 1600 rpm, 20 mV / s) and calculated Tafel plots of Pt-Cu / C (Examples 4-7) electrocatalysts after 200 cycles of in situ EA (0.05-1.2 V vs. RHE, 300 mV / s). The Pt:Cu chemical composition varied from Pt-poor to Pt-rich in the order (a) Example 4 < (b) Example 5 < (c) Example 6 < (d) Example 7. The SA and MA and ECSACO measured at 0.9 V vs. RHE are shown in Table 2. [Figure 8] XRD of the various PtCu3 / C electrocatalysts (Examples 8-11) shows differences in the carbon support, with the carbon support with higher surface area (BET) providing better dispersion for similar Pt:Cu chemical composition and similar total metal loading (Pt+Cu). [Figure 9]CO stripping CV (0.1 M HClO4, Ar saturated, no rotation, 20 mV / s), ORR polarization curves (0.1 M HClO4, O2 saturated, ohmic resistance compensated, background current subtracted, 1600 rpm, 20 mV / s) of PtCu3 / C electrocatalysts (Examples 8-11) after 200 cycles of in situ EA (0.05-1.2 V vs. RHE, 300 mV / s) as well as calculated Tafel plots. The total metal loading (Pt+Cu) and Pt:Cu chemical composition were kept as constant as possible while the type of carbon support was varied: (a) carbon black with BET of 250 m2 / g (Example 8), (b) carbon black with BET of 800 m2 / g (Example 9), (c) carbon black with BET of 1000 m2 / g (Example 10), and (d) carbon black with BET of 1400 m2 / g (Example 11). The SA and MA measured at 0.9 V vs. RHE and the ECSACO are shown in Table 3. [Figure 10-1] (a) PtCu+CuO / C composites after GD reaction of Cu / C with K2PtCl4 in the absence (PtCu+CuO / C analog, Example 3) or presence (PtCu+CuO / C-CO analog, Example 2) of CO gas; and (b) XRD analysis of the PtCu3 / C electrocatalyst obtained after subsequent thermal annealing of both analogs (PtCu3 / C and PtCu3 / C-CO) at 800 °C under Ar atmosphere. [Figure 10-2] STEM BF and HAADF images of (c) PtCu+CuO / C (Example 3) and (d) PtCu+CuO / C-CO (Example 2) obtained after the GD step of the synthesis, and (e) PtCu3 / C and (f) PtCu3 / C-CO analogs obtained after subsequent thermal annealing at 800 °C under Ar atmosphere, while (g) and (h) show ECSACO compiled from CO stripping CV in 0.1 M HClO4 comparing both analogs PtCu3 / C (Example 3) and PtCu3 / C-CO (Example 2). ECSACO was measured after 200 cycles of in situ EA (0.05-1.2 V vs. RHE, 300 mV / s). [Figure 11]XRD spectra of (a) as-synthesized Pt+Ni / C (without CO gas, Example 13) and Pt+Ni / C-CO (with CO gas, Example 12) using the double passivation GD method, (b) Pt3Ni+PtNi3+Ni / C (Example 13) and PtNi3 / C-CO (Example 12) after thermal annealing; (c) as-synthesized Pt+Co3O4 / C (without CO gas, Example 15) and Pt+Co3O4 / C-CO (with CO gas, Example 14) using the double passivation GD method, and (d) Pt3Co+PtCo3+Co / C (Example 15) and PtCo3 / C-CO (Example 14) after thermal annealing. [Figure 12] XRD spectra of (a) CuO+Cu on ex situ partially passivated reduced graphene oxide precursor (Example 16); (b) PtCu+CuO on as-synthesized reduced graphene oxide using the double-passivated GD method (Example 16); (c) PtCu+PtCu3 on reduced graphene oxide after thermal annealing (Example 16). [Figure 13] 1) TiOxNy support particles (Example 17); 2) TiOxNy support particles with Cu metal particles precipitated thereon (Example 17); 3) XRD spectrum of PtCu+CuO on as-synthesized TiOxNy support particles using double passivation GD method (Example 17). [Figure 14] XRD spectra of 1) Cu+Cu2O+CuO / C precursor where C is carbon black with BET of 800 m2 / g (Examples 18 and 19); 2) Pd+Cu2O+CuO / C composite as-synthesized using double passivation GD method in the presence of H2 (Example 18); 3) Pd+Cu2O+CuO / C composite as-synthesized using double passivation GD method in the presence of CO (Example 19). [Figure 15] 1 is a flow chart showing the steps of the dual passivation GD method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0050] Detailed Description of the Invention The above and further objects, features, and advantages of the present invention will be more fully understood by reference to the following illustrative and non-limiting detailed description and exemplary embodiments of the invention.
[0051] The present method is a simpler and more economically favorable process for preparing electrocatalyst materials containing precious metals (precious metals may be abbreviated as "NM" herein) compared to prior art methods. The present method is based on a "double passivation" galvanic displacement (GD) synthesis method for producing high performance supported precious metal-M alloy electrocatalysts (M is the electrochemically less noble metal compared to the precious metal in the GD process).
[0052] As known to those skilled in the art, the nobility of a metal is determined by its standard potential (also called the "standard electrode potential" or "standard reduction potential"). The standard potential is the potential at standard conditions, i.e., when the effective concentration is 1 mol dm -3 Standard potential is a measure of the individual potential of a reversible electrode with a solute of 1 atm and a gas at a pressure of 1 atm. Values of standard potential for all common metals are given with reference to the standard hydrogen electrode (SHE) at 25 °C. Metals with higher standard potentials (i.e. more positive standard potentials) are more noble than metals with lower standard potentials. Thus, the nobility of one metal relative to another can be easily determined by the metal's position in the so-called galvanic series, which lists the individual metals based on their standard potentials. Tables of standard potentials are found, for example, in Allen J. Bard and Larry R. Faulkner: "Electrochemical Methods, Fundamentals and Applications" 2001, 2 ndEdition, ISBN 978-0-471-04372-0, John Wiley & Sons, Inc., pages 808-809, and thus the term "less noble metal", as used in this context, refers to the standard electrode potential difference between two metals in an electrolyte, a noble metal (NM) and an alloying (sacrificial "less noble") metal (M), where the less noble metal has a lower electrode potential than the more noble metal (noble metal) and therefore will be galvanically corroded (displaced). The noble metal is in an ionic state (cation) while the sacrificial less noble metal is in a metallic state passivated by an oxide layer.
[0053] The present "double passivation" method, which uses a GD reaction in a liquid medium between a less noble sacrificial metal M (generally referred to herein as M / S, where S is the support material) deposited on the surface of a support material and a precious metal precursor, provides high quality dispersions of precious metal-M alloy nanoparticles on the support particle surface. The double passivation GD method of the present invention is shown generally in Figure 1, which shows the addition of the precious metal precursor to a liquid (e.g., an aqueous M / S dispersion, where the M particles have an oxide layer on the free surface exposed to the liquid) saturated with an adsorbed gas (exemplified herein as carbon monoxide) that interacts with the precious metal. All steps (a)-(e) of the method, as well as the optional annealing step (f), are also shown in the flow chart of Figure 15 and are described in detail below.
[0054] The term "adsorbed gas" as used herein refers to a gas capable of adsorbing on precious metals and precious metal-M alloys, particularly gas capable of chemisorbing on metallic precious metals. The gas molecules are preferably capable of forming chemical bonds with metallic precious metal sites. Adsorbed gases are sometimes referred to herein as "capping gases," "shielding gases," or "passivating gases."
[0055] The first passivation in the present double passivation GD synthesis is the passivation of the M / S precursor (M = metal deposited on the support particle or metal that is partially oxidized) by the formation of a surface M oxide layer on the metal M: FIG. 1(a). The formation of the surface M oxide layer has the effect of passivating the liquid medium (electrolyte) / M interface, while the M / S interface remains oxide-free, and thus becomes the preferential path for electrons in the galvanic replacement reaction. In other words, the surface oxide layer of M is less conductive than the support particle, so that the electrons are forced to move through the support particle. As a result, the addition of the noble metal precursor does not cause galvanic replacement at the surface of the metal M itself, but rather starts to deposit the noble metal on the support particle, while the metal M with the passivating oxide layer on its surface is corroded. Preferably, the entire surface of the metal M exposed to the liquid medium is passivated by the oxide layer.
[0056] The second passivation is the capping (also called shielding) of the precipitated noble metal and / or noble metal-M alloy nanoparticles by adsorbed gases adsorbed on the surface of the newly formed precipitated noble metal and / or noble metal-M alloy nanoparticles, see FIG. 1(b). The method exploits the noble metal-adsorbed gas interaction, where the gases adsorbed on the noble metal are used as capping agents to limit the growth of the noble metal nanoparticles during the GD reaction. The capping of the precipitated noble metal nanoparticles inhibits further deposition of the noble metal on the already formed noble metal and / or noble metal-M alloy nanoparticles, which in turn leads to the formation of new noble metal and / or noble metal-M alloy nanoparticles at new sites on the support particles. This approach not only results in the synthesis of very small and well-dispersed already precipitated nanoparticles, but is also very energy efficient and does not require an additional step for any surfactant removal.
[0057] FIG. 1(c) shows the GD deposition of precious metals in the absence of adsorbed gas, where the precipitated nanoparticles of precious metal and / or precious metal-M alloy grow into larger particles.
[0058] The present dual passivation GD method for preparing supported precious metal-M alloy nanoparticle composites (where M is a sacrificial metal that is galvanically substituted to precipitate the precious metal) is described in detail below and includes the following steps (shown in FIG. 15 ):
[0059] (a) In a first step, a precursor material is provided, generally described as M / S, which is a crystalline metal M on an electrically conductive support material S. The metal M is a metal less noble than the noble metals in the ionic state, meaning that the metal M has a lower standard electrode potential than the noble metal ion. Suitably, the metal M is one or more metals selected from the following group: Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Mo, W, Zn, Y, Gd and Pd, preferably Cu, Ni, Co, Fe, Ag, Mo, W, Zn, Cr, Pb, Ti, and even more preferably Cu, Ni, Co. The precursor M / S can be produced by any commonly known method for depositing metals on a support material, such as sol-gel, impregnation, chemical precipitation, pulse combustion (thermoacoustic reactor), etc. The metal M can be deposited on the support material in any shape and form. The particle size and particle size distribution of the metal M on the carbon support are not critical and can vary from nanometer size to micron size, e.g., from about 1 nm to about 20 μm, e.g., from 50 nm to about 20 μm. In fact, one important advantage of the process of the present invention is that the metal particles M in the M / S precursor composite do not have to be nanosized, but may be present in the micron size range. In addition, the M / S precursor composite in which the metal M is in the form of nanoparticles (e.g., 1-2 nm) on the support particles also showed the important effect that the as-synthesized product resulting from the present double passivation GD method contains very homogeneously distributed nanoparticles. The M / S precursor composite in which the metal M is in the form of nanoparticles (e.g., 1-2 nm) can be obtained using a thermoacoustic / pulse combustion reactor, any other method known in the art.
[0060] The M / S precursor material can be machined, such as by ball milling or grinding, in the presence of oxygen, and during this machining process, the metal particles on the support material can be oxidized or at least partially oxidized on their surfaces. Alternatively, the M / S precursor can be annealed in the presence of oxygen, thereby forming a metal oxide on at least a portion of the surface of the metal M. The partially oxidized M / S precursor can also be obtained from the synthesis method itself, for example by a thermosonic / pulse combustion reactor. Such an initially formed oxide layer on at least a portion of the metal M surface of the M / S precursor, generally referred to as M+MO / S, is described herein as an ex-situ passivation oxide layer. It is understood that the ex-situ M oxide layer can be formed by any known oxidation method. In this application, the term M / S precursor is also understood to include at least a partially oxidized metal M (M+MO / S) on a support material, unless otherwise stated.
[0061] The support material (S) is a particulate material that is more electrically conductive than any formed passivating M oxide layer of the metal M deposited on its surface. -15 S / cm, preferably 10 -7 The support material should have an electrical conductivity of greater than 0.03 S / cm, most preferably greater than 0.03 S / cm. The support material should be a stable and inert material that can withstand the synthesis conditions and the conditions in the electrochemical cell in which the deposited precious metal-M alloy nanoparticle material is used as a catalyst. Additionally, the support material should withstand high temperatures (>1200°C). Preferably, the support material has an electrical conductivity of at least 10 m 2 / g, e.g., at least 20m 2 / g, or at least 50m 2 / g. The support material (S) may be an electrically conductive carbon material, a conductive ceramic material, or a conductive composite material. The carbon support material may be selected from the group consisting of carbon black, carbon nanotubes (CNTs), graphene, graphite, or other conductive carbon materials, and modifications / derivatives thereof. The carbon support material has a surface area of at least 10 m 2 / g, preferably at least 20m 2 / g, more preferably at least 50m 2 The carbon support should have a surface area of at most 3000 m 2 / g, e.g., at most 1000m 2 / g, or at most 800m 2 / g, e.g., at most 500m 2 / g, at most 250m 2 / g, at most 200m 2 / g, or at most 150m 2 For example, the carbon support may have a surface area of 10 m 2 / g~3000m 2 / g, preferably 10m 2 / g~1000m 2 / g, e.g., 20-800m 2 / g, or 50-200m 2 The surface area is 1 / g. The surface area is measured by the BET method (Brunauer-Emmett-Teller method) 2 can be determined via physical adsorption of
[0062] The ceramic support material may be an electrically conductive ceramic, such as antimony tin oxide (ATO, Sb 2 SnO 5 ), fluorine-doped tin oxide (FTO, F:SnO 2 ), indium tin oxide (ITO, (In 2 O 3 ):(SnO 2 )) or titanium oxynitride (TiO x N y The ceramic support material is at least 10 m 2 For example, the ceramic support may have a surface area of 10 m 2 / g~200m 2 / g, e.g., 10m 2 / g~100m 2 The surface area is 1 / g. The surface is measured by the BET method (Brunauer-Emmett-Teller method). 2The surface area of the support material may be determined via physical adsorption of the carbon support material. The support material may also be a composite material, for example a ceramic-carbon composite. The surface area of the composite material may be as given above for the carbon support material.
[0063] (b) The M / S precursors, possibly including an ex situ passivated oxide layer (M+MO / S precursors), are suspended in a liquid medium, preferably an aqueous medium. The water can be tap water, but is advantageously distilled or deionized water (high purity water), since salts present in tap water can affect the experimental conditions. The liquid medium can also be an alcohol with 1 to 7 carbon atoms: CH 4 O~C 7 H 16 O, preferably C 1 ~C 3 Alcohol:CH 4 O~C 3 H 8 O, n H 2n+1 The liquid medium may also be based on water-miscible alcohols having 1 to 7 carbon atoms: CH 4 O~C 7 H 16 The pH of the liquid may be a mixture of O and M. The pH of the liquid may be such that, when the M / S precursor is suspended in the liquid, an oxide layer of the metal M is thermodynamically formed on the surface of the metal M (referred to herein as in situ passivation), resulting in the formation of passivated MO. y The metal M may be adjusted to form a stoichiometric M / S suspension, where y is greater than 0 and up to the stoichiometric M oxide value. Throughout this specification, a passivated metal M will be understood to have an oxide layer on at least the entire surface exposed to the liquid. In electrochemistry, a Pourbaix diagram, also known as a potential / pH diagram or pE / pH diagram, illustrates the possible stable phases of an aqueous electrochemical system. A Pourbaix diagram is represented by the notation of two axes, E H The vertical axis is the voltage potential against the standard hydrogen electrode (SHE) calculated by the Nernst equation, and the E H The horizontal axis is expressed as H +It is written pH for the -log function of ionic activity. The Pourbaix diagram shows the following regions (pH): where the metal is not attacked (dead zone), where it is passivated by forming a stable coating of oxide (or other salt) on the surface, or where it is attacked (corrosion zone). The formation of the passivated metal oxide MO on the metal M occurs thermodynamically at the liquid-metal interface, as the pH in the suspension is adjusted according to the oxide formation conditions. As a rule of thumb, if the oxide formation occurs thermodynamically at a higher pH, a more basic medium is required. Thus, for example, Ni and Co require a higher pH for the formation of the oxide layer than, for example, Cu. It should be noted that the time of formation of the in situ passivated M oxide layer may be different. Some metals may be oxidized quickly and the oxide forms immediately upon suspension of the M / S precursor in the liquid medium. Other metals may be oxidized more slowly and require more time for the passivation reaction to be completed. The formation of the M oxide can occur immediately after suspending the M / S in the liquid medium, for example, after 1 minute, 15 minutes, or even after 1 hour. The time for oxide formation should be less than one week, preferably up to one day, most preferably up to three hours. The precursor may also be at least partially passivated ex-situ before being suspended in the liquid medium. In such a case, the liquid medium should have a pH at which a passivated M oxide layer is maintained. The skilled person can find the suitable time and pH required for the formation of a passivation layer on a particular metal M by using routine work, see also the examples. Tests carried out by the inventors have demonstrated the formation of a passivated M oxide layer on M / S precursors, see tests 1-4 (described below) and Figures 3a) and b).
[0064] In the following, a suspended supported metal M having at least a passivating M oxide surface layer (formed ex situ and / or in situ) is generally referred to herein as MO. y / S, where y is >0 to the stoichiometric value of M oxide. It is to be understood that the oxide layer is formed at least on the entire surface exposed to the liquid medium, i.e. at the liquid medium-metal interface metal surface. The mass concentration of the M / S precursor in the liquid medium may vary. In general, a suitable rate of addition of the M / S precursor to the liquid forming the suspension is between 10 mg / L of liquid and 250 g / L. For practical reasons, the amount of M / S precursor in the liquid suspension may be at least 1 g / L, for example at least 5 g / L or 10 g / L.
[0065] (c) the metal supported on the support material has an ex-situ and / or in-situ passivating oxide layer; y The Mg / S suspension is supplied with a gas that interacts with the precious metal. The gas may be supplied by adding it to the liquid from an external source (e.g., gas purging) or it can be formed at least partially in situ. The gas purging is understood to bubble or disperse the gas in the liquid medium. The gas purging is preferably continued until the gas in the liquid is saturated. The expression "gas that interacts with the precious metal" is understood as a gas that (selectively) adsorbs on the precious metal surface and / or the precious metal-metal M alloy surface, also described herein as "adsorption gas", "capping gas", "shielding gas" and "passivation gas". Preferably, the suspension is continuously mixed during the addition of the adsorption gas by mechanical stirring, for example by a magnetic stirrer, a pitched blade turbine stirrer, a propeller stirrer, a Rushton turbine stirrer or other known stirrers. The stirrer speed can vary, for example, within the range of 5 rpm to 1000 rpm (rpm = revolutions per minute), for example, 10 rpm to 250 rpm. Mixing may also be achieved by stirring with continuous bubbling of the adsorbent gas. The adsorbent gas may be carbon monoxide gas (CO), hydrogen gas (H 2 ), hydrogen sulfide gas (H 2 In syntheses where the noble metal is Pt, Ir, Rh or Pd, the adsorbed gas is preferably CO or H 2When the noble metal is Au, the adsorption gas is preferably H 2 S or methanethiol. Therefore, the combination of noble metal + adsorption gas for synthesis is Ir + CO gas; Ir + H 2 Gas; Rh+CO Gas; Rh+H 2 Gas; Pd+CO Gas; Pd+H 2 Gas; Pt+CO Gas; Pt+H 2 Gas; Au+H 2 S; Au+methanethiol.
[0066] Preferably, the adsorbed gas in the synthesis with Pt as the noble metal is CO. In a liquid medium containing water-soluble alcohol, platinum may decompose the alcohol to form a CO gas intermediate. Thus, the capping agent (gas) may also be formed at least partially in situ to reduce or avoid the addition of CO gas from an external source. Alternatively, the adsorbed CO gas may be supplied from both an external source in combination with in situ formation. Correspondingly, as explained above, the suspension may be stirred to achieve uniform conditions throughout the suspension.
[0067] (d) Passivated MO y After formation of a suspension of 1000 / S and saturation of the suspension with the absorbing gas, the method comprises the steps of: yThe method further comprises the addition of a precious metal precursor (i.e. a precious metal cation) to the / S suspension. The addition of the precious metal precursor results in the precipitation of crystalline precious metal nanoparticles and / or crystalline precious metal-M alloy nanoparticles on the support particles by a galvanic replacement reaction, as explained above. In order to ensure that the formed precious metal and / or precious metal-M alloy nanoparticles are passivated by (selective) adsorption of the passivating gas, it is advisable to maintain saturation of the adsorbed gas in the suspension during the addition of the precious metal precursor. Suitable precious metal precursors include the precious metal salts soluble in aqueous media or alcohols as specified above in step (b) and their corresponding acids. The precious metal precursor can be added in solid form or as a solution containing the dissolved precious metal precursor. Halide salts of precious metals (NM2H4H4H5H2O4) can be added in the form of a mixture of 100% niobium and 100% niobium. n+ Y n ) (both hydrated and anhydrous), alkali metal halide salts (A m NM n+ Y m+n ) (both hydrated and anhydrous), or the corresponding hydrohalic acids (H m NM n+ Y m+n ), many of which are particularly preferred since they are generally water soluble (NM=noble metal; m=typically 1 or 2, n=typically 1, 2, 3 or 4, X=alkali metal cation Li + , Na + , K + ;Y=halide F - , Cl - , Br - , I - The rate of addition of the precursor is not critical and the precious metal may be added all at once or, for example, by using a pump whereby the entire amount of the precious metal precursor is added over time. Preferably, the mixing is carried out in a manner such that the precious metal precursor is a mixture of MO yThe rate of addition of the noble metal precursor should be appropriate in relation to the rate of addition so as to react equally throughout the entire noble metal / S precursor. This results in a uniform and well-dispersed growth of noble metal nanoparticles and / or noble metal-M alloy nanoparticles on the support material without substantial local variations in metal loading. The rate of addition of the noble metal precursor may be at least 1 mL / h, for example, 10 mL / h to 3600 mL / h, for example, 50 to 350 mL / h. Without being bound by theory, it is believed that a small difference in standard electrode potential between the noble metal cation and the less noble metal leads to a slower reaction rate compared to when the difference in standard electrode potential between the noble metal cation and the less noble metal is large. Based on this, when the difference in standard electrode potential between the noble metal cation and the less noble metal is small, the rate of addition of the noble metal precursor should be slower compared to the rate of addition when the difference in standard electrode potential between the noble metal cation and the less noble metal is large. The amount of the noble metal in the suspension is preferably about 1000 to 20 ... y The amount of precious metal precursor added per mass of M / S may vary depending on the desired composition of the precious metal-M alloy nanocomposite final product. The precious metal:M ratio (i.e., the chemical composition of the alloy product produced) will vary depending on: 1) the total mass of precious metal precursor added (i.e., it can replace various percentages of the available M in the M / S precursor), 2) the amount of M (wt%) in the M / S precursor, and 3) the stoichiometry of the galvanic replacement reaction between the precious metal and M (e.g., 1:1 stoichiometry between Pt and Cu: TIFF0007601853000001.tif4128). The suspension may be continuously mixed during the addition of the precious metal precursor by mechanical stirring, for example by a magnetic stirrer, pitched blade turbine stirrer, propeller stirrer, Rushton turbine stirrer, or other known stirrers. The stirrer speed may vary, for example, from 5 rpm to 30000 rpm (rpm = revolutions per minute), for example, in the range of 10 rpm to 1000 rpm. Mixing may also be achieved by stirring by continuous bubbling of the adsorbed gas. Ultrasonic stirring is also possible if the process is carried out under high pressure or, see step (b) above, if the adsorbed gas is formed in situ or if the capping agent is not a gas.
[0068] (e) After all the precious metal precursors have been added to the reaction mixture and, optionally, the suspension is kept mixed for a period of time until the reaction is complete, the suspended product is then separated from the liquid and the product is washed, for example, by redispersing the reaction product in a fresh liquid medium. Separation can be performed by any known means, such as filtration, centrifugation, decantation, etc. Separation by centrifugation is preferred. Centrifugation and washing may be repeated, for example, 2-4 times, or more if necessary, until all soluble by-products have been removed from the product. Any washing step may involve heating the washing liquid, for example boiling the suspension. Any remaining impurities can be detected using EDX SEM, but crystalline impurities can also be seen in the XRD diagram, which should show only crystalline phases containing the precious metal, the less noble M, the O present in the metal oxide, and the elements of the support material. The precious metal or precious metal-M alloy+MO thus obtained is y The M / S reaction product is then dried according to commonly known methods. The as-synthesized product contains precipitated noble metal and / or noble metal-M alloy nanoparticles, residual MO y The MO y The particles are less noble metal M particles at least partially having an oxide surface layer (so that y is greater than 0 and up to the stoichiometric M oxide value). In some embodiments, the as-synthesized product comprises precipitated noble metal and / or noble metal-M alloy nanoparticles, with residual MO y The reaction products are characterized by a very good dispersion of the precipitated noble metal nanoparticles and / or noble metal-M alloy nanoparticles on the support material, with a narrow size distribution of only a few nanometers, mostly less than 10 nm or even 5 nm. Thus, in contrast to the reaction products formed by conventional GD methods, the nanoparticles formed by the present double passivation GD method are not in the shape of core-shell type particles. Rather, they are composed of precipitated noble metal nanoparticles and / or noble metal-M alloy nanoparticles and residual MO. y The particles are distributed spaced apart on the support material.
[0069] (f) Dried precious metals and / or precious metal-M alloys + residual MO y The / S product can be further processed by thermal annealing under an inert or reducing atmosphere. The purpose of the thermal annealing is to remove the remaining MO which can be thermally reduced to element M. y The goal of the present invention is to alloy the particles with precious metal and / or precious metal-M alloy nanoparticles and align the precious metal-M alloy crystal lattice as much as possible. The dried reaction product is placed in an inert refractory crucible that is sealed in a high temperature stable container such as a quartz tube and heated with an oxygen-free gas such as an inert gas (e.g., Ar), or a reducing gas (e.g., CO), or a mixture of an inert gas and a reducing gas, e.g., Ar / H 2 The thermal annealing temperature is set at 100° C., and the temperature is set at 100° C. y The level of reduction of Pt to M. Without being bound by theory, it is believed that when carbon is used as the support material, the metal oxide is reduced by reaction with the carbon support material. Typically, the annealing temperature is 450-1200°C, e.g., 500-900°C, preferably 600-800°C. The treatment time and temperature may vary, and may be from a few seconds to several weeks. For practical reasons, the thermal annealing treatment time may be from 1 minute to 1 week, preferably 1 minute to 1 day. The annealing treatment time varies depending on the temperature and the metals in the alloy. When annealing at 450°C, the alloying process may be very slow, especially for certain metals that do not mix very well (e.g., Ni is more difficult to alloy with Pt than Cu). On the other hand, when higher temperatures are used, e.g., 800°C or more, the reaction rate may be very fast, so that only a second or a few seconds are sufficient at the higher temperatures. The sealed container is filled with an inert gas (e.g., Ar or N) throughout the thermal annealing treatment. 2 ) or reducing gas (e.g., Ar / H 2Preferably, the furnace is purged with a (5%) mixture of 10 ...
[0070] It may be important to control the cooling rate, since slower cooling may result in more aligned nanoparticle crystal lattices. Thus, cooling may be as slow as 0.1 K / min to as fast as possible cooling in liquid nitrogen. Typically, the cooling rate may be 1-20 K / min, e.g., 3-10 K / min. It should also be understood that alignment of nanocrystalline particles may be achieved during thermal annealing, before cooling, or in combination with controlled cooling, e.g., by using different annealing temperatures and holding times.
[0071] The GD synthesis according to the present invention, i.e. steps b) to e), can be carried out at room temperature and pressure (1 atm). The temperature of the synthesis steps can also be higher than room temperature. The advantages of increasing the temperature are: 1) a faster reaction rate; 2) a higher solubility of most noble metal precursors (salts and their corresponding acids); on the other hand, the solubility of gases decreases with increasing temperature. However, the process can be carried out under higher than ambient pressure, which can increase the solubility of most gases, thus avoiding the decrease in solubility of gases at higher temperatures.
[0072] The double passivated GD synthesis of the present invention has several advantages over prior art polyol-type synthesis methods: (i) the method of the present invention can be carried out in aqueous and / or aqueous alcoholic media (i.e., the method does not involve complex organic solvents); (ii) the method of the present invention can be carried out at room temperature and atmospheric pressure, as it utilizes spontaneous processes (first passivation, GD reaction, and second passivation), and is very energy efficient; (iii) the synthesis and precipitation of the nanoparticles (dispersion at the surface of the support material) occur within the same synthesis step (the noble metal nanoparticles grow on the surface of the support material itself); (iv) the precursors used in the present synthesis are not typical precursors used in prior art methods (e.g., Pt(AcAc) used in polyol-type synthesis). 2 ), is significantly cheaper than the first passivation; and further (v) the method is easily scalable to gram batch scale, which is important for commercial production. The double passivation GD synthesis of the present invention also has an important advantage over the prior art GD synthesis methods: the size and morphology of the sacrificial less noble metal is not important, since the GD reaction does not take place on the less noble metal, and instead this electronic pathway is blocked by the first passivation. This essentially simplifies the synthesis of the precursor M / S materials and improves their commercial availability. On the other hand, the second passivation blocks the second electronic pathway, blocking the GD reaction even at the initial stage of the GD-formed precious metal nanoparticles and / or precious metal-M alloy nanoparticles. The present double passivation process, in which two of the three paths of electrons (first through the less noble sacrificial metal and second through the precious metal nanoparticles and / or precious metal-M alloy nanoparticles) are blocked, essentially allows for complete dispersion of the precious metal nanoparticles and / or precious metal-M alloy nanoparticles, since the only remaining path of electrons is through the support material. Thus, during the addition of the precious metal precursor and the GD reaction, precious metal nanoparticles and / or precious metal-M alloy nanoparticles are always formed on new spots of the support material, which cannot be achieved by any other known method.
[0073] Moreover, the simple flexibility in moving from one material design to another is not possible in other methods. Previously known methods for depositing nanoparticles of polyols on support materials as well as other methods require the adjustment of the zeta potential to ensure that the precious metal nanoparticles and / or precious metal-M alloy nanoparticles and the support material attract each other while the precious metal nanoparticles and / or precious metal-M alloy nanoparticles repel each other. Based on the prior art methods, none of them can fully adjust the zeta potential because it is difficult to fully control the zeta potential, and there will be at least some precious metal nanoparticles and / or precious metal-M alloy nanoparticles that do not repel and end up agglomerating together. The present double passivation GD process does not need to rely on the zeta potential, and therefore the method can be easily adapted to various material designs (e.g., changing the NM and / or sacrificial metal M, adjusting the support material S, adjusting the total NM+M loading, adjusting the ratio of NM to less noble metal M). This is because the precious metal nanoparticles and / or precious metal-M alloy nanoparticles formed via the GD reaction are directly crystallized on the surface of the support material where the NM precursor salt accepts electrons. Thus, the double passivation method only requires blocking other available pathways for electron transfer during the GD reaction.
[0074] The crystalline noble metal nanoparticles and / or noble metal-M alloy nanoparticle materials on the support particles S produced by the method including the thermal annealing step include an alloy of a noble metal selected from Pt, Ir, Rh, Pd, or Au with one or more metals M selected from Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Mo, W, Zn, Y, Gd, and Pd. The noble metal-M alloy nanoparticles may have an average particle size in the range of 1-200 nm. If the particle size is too small, the stability of the noble metal-M alloy nanoparticles (e.g., platinum alloy catalysts under fuel cell operation) is very low. Particles with a diameter of less than 1 nm may not be very stable when used as catalytic materials. On the other hand, if the particle size is too large, the noble metal is not fully utilized as a catalyst because only the surface atoms are involved in the catalytic reaction, resulting in low mass activity. The resulting noble metal nanoparticles and / or noble metal-M alloy nanoparticles may therefore have an average particle size in the range of about 1 to about 20 nm, preferably 2 to 7 nm, e.g., 3 to 5 nm. The products prepared according to the present method are particularly suitable as electrode catalyst materials in electrochemical energy conversion devices.
[0075] The Pt-M alloys on the support material S produced by the method of the present invention are particularly suitable as electrocatalyst materials (both cathode and anode) in PEM fuel cells, while for example supported iridium-M alloys can be used in PEM electrolysers for the cathode (the reverse reaction to PEM fuel cells). It has also been reported that Au-Cu alloys act as catalysts for the reduction of carbon dioxide. Thus, precious metal alloys find wide application in electrochemical energy conversion devices.
[0076] The supported precious metal nanoparticles and / or precious metal-M alloy nanoparticle products produced by the present method (including the heat treatment step) are suitable for use as catalytic materials in electrochemical energy conversion devices such as electrolytic cells (e.g., proton exchange membrane (PEM) electrolyzers) and fuel cells (e.g., PEM fuel cells). Similarly, the residual MO nanoparticles produced by the present method are suitable for use as catalytic materials in electrochemical energy conversion devices such as electrolytic cells (e.g., proton exchange membrane (PEM) electrolyzers) and fuel cells (e.g., PEM fuel cells). yThe as-synthesized (non-heat-treated) supported noble metal-M alloy nanoparticles combined with particles (y is >0 to the stoichiometric value of the corresponding metal oxide) are also suitable for use as catalytic materials in electrochemical energy conversion devices such as electrolytic cells (e.g., proton exchange membrane (PEM) electrolyzers) and fuel cells (e.g., PEM fuel cells). As is generally known in the art, the as-prepared electrocatalytic materials may have to be activated prior to use, for example, by removal of less noble metals on the surface of the nanoparticles, generally referred to as "catalytic activation". Catalytic activation of electrocatalytic materials is generally described below.
[0077] All M / S precursor materials, MO y / S (y is >0 to the stoichiometric value of the corresponding metal oxide), noble metal nanoparticles and / or noble metal-M alloy nanoparticles on the substrate material S, and residual MO on the substrate material S. y For as-synthesized (non-thermally treated) supported precious metal nanoparticles and / or precious metal-M alloy nanoparticles combined with the zeolite particles (y is >0 to the stoichiometric value of the corresponding metal oxide), the support material S may be a carbon support material selected from the group consisting of carbon black, carbon nanotubes (CNTs), graphene, graphite, or other conductive carbon materials and modifications thereof, which are generally referred to as M / C precursor materials and MO / C precursor materials. y Note that the M / S precursor materials may sometimes be written as y > 0 to the stoichiometric value of the corresponding metal oxide. Similarly, all of the above M / S precursor materials, MO y / S (y is >0 to the stoichiometric value of the corresponding metal oxide), noble metal nanoparticles and / or noble metal-M alloy nanoparticles on the substrate material S, and residual MO on the substrate material S. y For as-synthesized (not heat-treated) supported noble metal nanoparticles and / or noble metal-M alloy nanoparticles combined with the y-particles (y is >0 to the stoichiometric value of the corresponding metal oxide), the support material S can be, for example, antimony tin oxide (ATO), fluorine-doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x Ny The same applies, mutatis mutandis, to the conductive composite support material S.
[0078] In a particular embodiment of the present invention, the supported noble metal-M alloy nanoparticles are platinum alloy electrocatalysts, which are catalysts for catalyzing electrochemical reactions. For example, the catalysts are catalysts for the anodic hydrogen oxidation reaction (HOR) and / or ORR. Preferably, the catalysts are ORR catalysts. For example, the catalysts are fuel cell catalysts, i.e., catalysts employed in the anode (catalyzing HOR) or cathode (catalyzing ORR) of fuel cells, such as PEM fuel cells.
[0079] As-synthesized platinum alloy catalysts (especially after thermal annealing and further enrichment of M) generally exhibit very low catalytic activity (e.g., in ORR) unless they undergo further treatment before use. After synthesis, most of the catalyst surface is often covered with less noble metal atoms that block access to platinum active sites at the surface of the platinum alloy. Thus, the less noble metals at the surface of the platinum alloy catalyst are often also referred to as impurities, since they reduce the catalytic activity. Thus, platinum alloy catalysts usually need to be treated to remove the less noble metals from the surface of the catalyst; that is, dealloying or leaching of the less noble metals from the surface of the platinum alloy is required. In this way, a platinum alloy catalyst is achieved that has a platinum alloy composition inside, but the outermost atomic layer of the platinum alloy catalyst is ideally composed of only platinum, thus forming a platinum overlayer. Such a platinum overlayer is often referred to as a "platinum skin" or "platinum skeleton" overlayer (thickness may range from a single atomic layer of platinum up to about 2 nm). Removal of the less noble metal from the catalyst surface makes the catalytically active platinum accessible and increases catalytic activity, hence the treatment is sometimes referred to as "catalyst activation".
[0080] However, while the less noble metals of platinum alloy catalysts need to be removed from the catalyst surface, they must not be removed from the interior of the platinum alloy catalyst. The presence of the less noble metals in the interior of the platinum alloy alters the structural and / or electronic properties of the platinum alloy compared to platinum-only materials, thus causing effects known as the ligand effect and / or strain effect. For example, the ligand / strain effect, together with better utilization of platinum, has been blamed for the improved activity of platinum alloy catalysts compared to platinum-only catalysts in terms of ORR. That is, the less noble metals can induce strain and thus modify the structure of the platinum overlayer, which is important for the catalytic performance of platinum alloy catalysts. Thus, complete removal of the less noble metals from the platinum alloy ultimately results in a decrease in catalytic activity.
[0081] For example, one typical method to enhance the activity of platinum alloy catalysts used to catalyze the ORR can be performed by so-called electrochemical activation. A typical electrochemical activation method employed for screening of as-synthesized platinum alloy electrocatalysts is performed using an electrochemical cell. This is therefore sometimes referred to as in situ electrochemical activation (in situ EA) since the activation is performed inside the electrochemical cell where catalytic activity measurements can be performed or where the catalyst is utilized to catalyze a desired reaction. Such activation is different from the activation used prior to use in an electrochemical conversion device. Hence, in situ EA is used for screening purposes only.
[0082] Standard laboratory electrochemical cells, e.g., Allen J. Bard and Larry R. Faulkner: "Electrochemical Methods, Fundamentals and Applications" 2001, 2 ndA three-electrode half-cell configuration is usually adopted, as described in Electrochemical Methods, Vol. 13, No. 1, pp. 24-27, 1999. Edition, ISBN 978-0-471-04372-0, John Wiley & Sons, Inc., Chapter 1.3.4, in particular pages 24-27. In each electrochemical cell, a platinum alloy catalyst is brought into electrical contact with an electrode, in particular the working electrode. For this purpose, the so-called thin-film method is usually applied, i.e. a thin film of catalytic material is deposited on the working electrode. This can be achieved by preparing a suspension of the platinum alloy catalyst, which is then dried on the surface of the working electrode. A thin film of the catalyst is thus obtained, in electrical contact with the working electrode. When determining the catalytic activity of a catalyst, it is beneficial to use a rotating disk electrode (RDE) as the working electrode. The basic principles of the RDE are described, for example, in Allen J. Bard and Larry R. Faulkner: "Electrochemical Methods, Fundamentals and Applications" 2001, 2 ndEdition, ISBN 978-0-471-04372-0, John Wiley & Sons, Inc., Chapter 9.3. Measurements of thin films deposited on an RDE as a working electrode are called thin film rotating disk measurements (TF-RDE). After the platinum alloy catalyst is brought into electrical contact with the working electrode of the electrochemical cell, the electrochemical cell is fully assembled and the working electrode with the catalyst on top is brought into contact with a suitable electrolyte. Electrochemical activation can then be performed by subjecting the catalyst to an external current and / or potential. That is, the catalyst can be subjected to, for example, galvanostatic, potentiodynamic, or potentiodynamic conditions, or similar conditions. For this purpose, the electrodes of the electrochemical cell can be controlled using a potentiostat, although in principle other power sources may be used. In most cases, electrochemical activation is performed by subjecting the platinum alloy catalyst to potentiodynamic cycles, i.e. cyclic voltammetry (CV). This allows precise control of the potential window, the number of potential cycles, and the scan rate. By subjecting the platinum alloy catalyst to a suitable current and / or potential in an electrochemical cell, dissolution of the less noble metal in the platinum alloy catalyst is achieved, thus resulting in dealloying and / or leaching of the less noble metal from the surface of the platinum alloy catalyst. For this purpose, a potential sweep applied during cyclic voltammetry is very effective. The dissolved less noble metal accumulates in the electrolyte. In this way, a platinum overlayer can be obtained, increasing the activity of the catalyst towards ORR.
[0083] The ORR activity of a platinum alloy catalyst can be expressed by specific activity (SA) and / or mass activity (MA). Specific activity is the activity normalized to the catalyst surface area. That is, the activity is normalized to the so-called electrochemically active surface area (ECSA), which in the case of ORR (and / or HOR) is determined by the platinum atoms present on the surface of the platinum alloy catalyst. The ECSA thus corresponds to the platinum-surface area of the platinum alloy catalyst. In the case of a platinum alloy catalyst containing a carbon support, the carbon support does not contribute to the ECSA, since it does not catalyze the ORR. MA is the activity normalized to the mass of platinum present on the platinum alloy catalyst. Thus, SA refers to the so-called reaction current of the ORR at a given potential (typically 0.9 V vs. RHE; RHE = reversible hydrogen electrode), normalized by the ECSA. This is generally expressed as [mA / cm 2 ]. MA refers to the so-called reaction current of the ORR at a given potential (typically 0.9 V vs. RHE) normalized by the mass of platinum present in the platinum alloy catalyst. This is generally expressed in [A / mg Pt The ECSA can be determined electrochemically, for example, via the adsorption of a carbon monoxide monolayer on the catalyst surface (the adsorption of CO is carried out at a controlled potential, for example 0.05 V vs. RHE) and subsequent oxidation of the monolayer via cyclic voltammetry (the so-called CO electrooxidation or CO stripping experiment). The charge required for CO to be oxidized can then be used to calculate the ECSA. CO is calculated. ECSA CO is generally expressed as [m 2 / g Pt Specific activity and mass activity are related to each other through the ECSA of the catalyst by the formula: MA = SA · ECSA.
[0084] The meaning and measurement of SA, MA, and ECSA are known to those skilled in the art. EXAMPLES
[0085] The invention is illustrated in the following Examples 1-17 with the Pt-M alloy system, where M is Cu, Ni, or Co and the precious metal is Pt. These examples use commercially available carbon supports, Vulcan XC72, Ketjen Black EC300J, Printex® XE2, and Ketjen Black EC600J, all of which have BET surface areas between 250 and 1400 m. 2 / g of carbon black material. The example shows reduced graphene oxide and TiO x N y The following examples should not be understood as limiting the invention, since the noble metal Pt may be alloyed with other less noble metals M, and the support material may be any other support material as defined above.
[0086] In the present Pt-M alloy embodiment, the strong interaction between CO (carbon monoxide) gas and Pt is used as a capping agent to limit the growth of Pt nanoparticles during the GD reaction. This approach not only results in the synthesis of very small and well-dispersed nanoparticles, but is also very energy efficient and does not require an additional step for the removal of any surfactant.
[0087] For the Pt-Cu alloy system, the novel synthesis involves three main steps: (i) preparation of a Cu crystalline phase and / or a partially oxidized (ex situ) copper oxide CuO crystalline phase on a carbon support, generally described herein as Cu+CuO / C. The Cu as sacrificial metal on the carbon support does not have to be in the form of nanoparticles, but can be of nm to micron size, as shown in FIG. 2a; (ii) GD reaction of the passivated CuO / C (where y is >0 to the stoichiometric copper oxide value) with a soluble Pt salt precursor in a liquid (e.g., aqueous system) (in situ and optionally ex situ) to obtain a PtCu+CuO / C composite, see FIG. 2b); and (iii) subsequent thermal annealing under an inert / reducing atmosphere to alloy the remaining Cu (here in the form of thermally reduced CuO) for further enrichment of Pt alloy nanoparticles, see FIG. 2c). Furthermore, in Fig. 2d) an XRD analysis (XRD = X-ray diffraction pattern) (bottom) of precursor Cu on carbon support is shown, which shows a relatively narrow and high peak for Cu according to the Scherrer equation describing the relationship between XRD peaks and crystallite size, i.e., a relatively large crystallite size for Cu. The middle XRD analysis shows the GD product before thermal annealing, where the CuO phase is clearly identified along with the PtCu alloy phase, and the PtCu alloy peak is low and broad, which indicates a very small crystallite size. The top XRD analysis shows the PtCuO phase after thermal annealing, where the CuO phase is clearly identified along with the PtCu alloy phase, and the PtCu alloy peak is low and broad, which indicates a very small crystallite size. 3 The resulting material consists of an alloy. The broadening of the peaks indicates that the grain size is very small. Figure 2e) shows the change in grain size distribution before and after thermal annealing, indicating a relatively narrow grain size distribution.
[0088] It was assumed that the same double passivation GD synthesis method could be used for gram-scale synthesis of Ni / C and Co / C instead of Cu / C. GD of Cu / C occurred efficiently in ultrapure water, whereas passivation of Ni and Co required pH adjustment with very low concentrations of KOH due to differences in the Pourbaix diagrams of each sacrificial metal. This indicates that the double passivation GD method can be used for various systems, but it is always good to consider i) the Pourbaix diagrams of the sacrificial metals supported on the substrate, which dictates the required pH, and ii) the differences in the formation, growth and properties of their oxides.
[0089] Examples 18-19 relate to the synthesis of supported Pd nanoparticle and CuO particle composites where CO and hydrogen gases are used as the adsorbed gases.
[0090] Powder X-ray diffraction (XRD) measurements of all samples were performed either on a PANalytical X'Pert PRO MPD diffractometer with a fully opened X'Celerator detector, Cu Kα1 radiation (λ=1.5406 Å), 2θ range 10°-60°, 0.034° steps per 100 s, or on a Siemens D5000 diffractometer, Cu Kα1 radiation (λ=1.5406 Å), 2θ range 10°-60°, 0.04° steps per s. Samples were prepared on zero background Si holders.
[0091] TEM analysis was performed on a probe Cs-corrected scanning transmission electron microscope Jeol ARM 200 CF equipped with a SDD Jeol Centuria energy dispersive X-ray (EDX) spectrometer. The operating voltage was set at 80 kV. High-angle annular dark field (HAADF) images were taken with inner and outer half angles of 68 and 180 mrad. The convergence angle was set at 25 mrad.
[0092] Analysis of particle size distribution: The software used was Image J, which allows measuring the particle size either manually or algorithmically depending on the distribution and whether the particles overlap. If they overlap, they are measured manually and the data is later grouped and arranged as a histogram on Microsoft Excel, later plotted in OriginLab.
[0093] When referring to SA, MA, and ECSA in this application, the respective values are experimentally determined via thin film rotating disk electrode measurements (TF-RDE) as described in the general description section of the specification. A detailed description of the experimental determination of SA, MA, and ECSA is provided in at least - Mayrhofer et al., "Measurement of Oxygen Reduction Activities via Rotating Disc Electrode Method: From Pt Model Surfaces to Carbon-Supported High Surface Area Catalysts." Electrochimica Acta 2008, 53, 3181-3188; and - Schmidt et al., "Characterization of High-Surface Area Electrocatalysts Using a Rotating Disk Electrode Configuration" J. Electrochem. Soc. 1998, 145, 2354-2359 Provided by.
[0094] These documents provide criteria for the determination of catalytic activity of electrocatalysts for ORR. The determination of HOR activity can also be performed by applying TF-RDE measurements. All measurements of SA, MA, and ECSA given in this application are performed according to the criteria described in said documents. The descriptions of the methods for determining SA, MA, and ECSA in said documents are incorporated herein by reference.
[0095] Test: Passivation of M precursors Test to demonstrate the formation of an in situ formed passivating oxide layer on metal M precursors on support particles. This test was carried out for Cu and Co on carbon support particles.
[0096] Test 1: Passivation of Cu / C with CO purging. In a two-neck round-bottom flask, a Cu / C mixture containing 14.1 wt% Cu (C: BET surface area 250 m 2 1 gram of carbon black (10 ... 2 The O / C composite was left to dry overnight at 50°C.
[0097] Test 2: Passivation of Cu / C with Ar purging. In a two-neck round-bottom flask, a Cu / C mixture containing 14.1 wt% Cu (C: BET surface area 250 m 2 1 gram of carbon black (CuO / g) was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). Afterwards, the suspension was first purged with Ar for 120 minutes. Afterwards, the suspension was filtered. The resulting Cu+CuO+Cu 2 The O / C composite was left to dry overnight at 50°C.
[0098] Figure 3a) shows the XRD spectra of the as-prepared Cu / C precursor, after suspension in water and purging with CO (Test 1), and after suspension in water and purging with Ar only (Test 2). The formation of Cu oxides is clearly observed in both tests, with a decrease in the metallic Cu peak but an increase in the Cu oxide phase. When carbon monoxide is introduced, it is indeed seen that there is less Cu phase and more oxide phase, which is consistent with the Pourbaix diagram. Although the pH was kept constant, the (open circuit) potential was higher for a more oxidizing gas such as CO (as opposed to an inert gas such as Ar), and this condition was shifted further into the region where passivation is promoted.
[0099] Test 3: Co / C passivation with CO purging. In a two-necked round-bottom flask, a Co / C mixture containing 14.1 wt% Co (C: BET surface area 250 m 2 1 gram of carbon black (1000 mg / g) was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged first with Ar for 45 minutes and then switched to CO for 75 minutes. The suspension was then filtered. The resulting Co+Co 3 O 4 The / C composite was left to dry at 50° C. overnight.
[0100] Test 4: Co / C passivation with CO purging, pH adjustment. In a two-necked round-bottom flask, a Co / C mixture containing 14.1 wt% Co (C: BET surface area 250 m 2 One gram of carbon black (1000 mg / g) was suspended in 100 mL of 0.001 M KOH (Merck). The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged first with Ar for 45 min and then switched to CO for 75 min. The suspension was then filtered and redispersed in fresh ultrapure water. After 15 min of mixing, the suspension was filtered again and the process was repeated for KOH neutralization a total of three times. The resulting Co+Co 3 O 4 The I / C composite was left to dry at 50° C. overnight.
[0101] Figure 3b) shows the XRD spectra of the as-prepared Co / C precursor, after suspension in water and purging with CO (Test 3), and after suspension in 0.001 M KOH and purging with CO (Test 4). The formation of Co oxides is clearly observed in both tests, with a decrease in the metallic Co peak but an increase in the Co oxide phase. It is further observed that while some Co oxides are formed in water, at basic pH the formation of the Co oxide phase is increased.
[0102] Example 1: In a two-neck round-bottom flask, Cu / C containing 25.5 wt% Cu (C: BET surface area 250 m 2 Between 1 and 6 grams of Cu / C (carbon black) were suspended in 100 mL (200 mL for 6 gram batches) of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min to degas it. Afterwards, the suspension was purged with Ar for 45 min. The suspension was then bubbled with CO gas for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO(g) for 15 min, 11 mL of 0.1MK per gram of Cu / C was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO(g). 2 PtCl 4 (Apollo scientific) was added. After all the Pt precursor was added to the reaction mixture, the suspension was filtered and redispersed in fresh ultrapure water. After mixing for 15 min, the suspension was filtered again and the process was repeated a total of three times. After the final filtration, the resulting PtCu+CuO / C electrocatalyst was left to dry overnight at 50 °C. The dried PtCu+CuO / C electrocatalyst powder synthesized in the presence of CO was mixed with Al 2 O 3The crucible was placed in a quartz tube, sealed and purged with Ar for 2 h. After 2 h (when the atmosphere inside the quartz tube was oxygen-free), the temperature was increased to 800 °C with a ramp of 10 K / min while continuously purging with Ar for the entire duration of the thermal annealing process. After 1 h at 800 °C, the temperature was cooled to room temperature with a ramp of 10 K / min to obtain PtCu, a quartz tube containing 20 wt% Pt and 18.8 wt% Cu. 3 The / C electrode catalyst was recovered.
[0103] Example 2: In a two-neck round-bottom flask, a Cu / C mixture containing 9.3 wt% Cu (C: BET surface area 250 m 2 Two grams of 0.1MK / g carbon black were suspended in 250 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 minutes, 3.3 mL of 0.1MK per gram of Cu / C was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. The rest of the synthesis was the same as in Example 1. PtCu containing 6.1 wt% Pt and 8.6 wt% Cu was added. 3 The / C electrocatalyst was finally recovered.
[0104] Example 3: In a two-neck round-bottom flask, a Cu / C mixture containing 9.3 wt% Cu (C: BET surface area 250 m 2 Two grams of 0.1MK / g carbon black were suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with Ar for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with Ar for 15 min, 3.3 mL of 0.1MK per gram of Cu / C was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with Ar. 2PtCl 4 (Apollo scientific) was added. The rest of the synthesis was similar to that in Example 1.
[0105] Example 4: In a two-neck round-bottom flask, a Cu / C mixture containing 14.1 wt% Cu (C: BET surface area 250 m 2 One gram of 0.1MK / g carbon black was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 minutes, 5 mL of 0.1MK was added by syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. PtCu containing 11.6 wt% Pt and 11.7 wt% Cu 3 The / C electrocatalyst was finally recovered.
[0106] Example 5: In a two-neck round-bottom flask, a Cu / C mixture containing 14.1 wt% Cu (C: BET surface area 250 m 2 One gram of 0.1MK / g carbon black was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 minutes, 10 mL of 0.1MK was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 All other conditions were the same as in Example 1. A PtCu / C electrocatalyst containing 19.5 wt % Pt and 7.3 wt % Cu was finally recovered.
[0107] Example 6: In a two-neck round-bottom flask, a Cu / C mixture containing 14.1 wt% Cu (C: BET surface area 250 m 2 One gram of 0.1MK / g carbon black was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 minutes, 12.5 mL of 0.1MK was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 All other conditions were the same as in Example 1. A PtCu / C electrocatalyst containing 24 wt % Pt and 5.5 wt % Cu was finally recovered.
[0108] Example 7: In a two-neck round-bottom flask, a Cu / C mixture containing 14.1 wt% Cu (C: BET surface area 250 m 2 One gram of 0.1MK / g carbon black was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 minutes, 15 mL of 0.1MK was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. Everything else was the same as in Example 1. A PtCu / C electrocatalyst containing 26 wt% Pt and 4.1 wt% Cu was finally recovered.
[0109] Example 8: In a two-neck round-bottom flask, a Cu / C mixture containing 33 wt% Cu (C: BET surface area 250 m 21–3 grams of 0.1MK / g carbon black were suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After 15 min of bubbling with CO, 15 mL of 0.1MK per gram of Cu / C was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. PtCu containing 26.8 wt% Pt and 25.2 wt% Cu 3 The / C electrocatalyst was finally recovered.
[0110] Example 9: In a two-neck round-bottom flask, a Cu / C mixture containing 33 wt% Cu (C: BET surface area 800 m 2 Between 1 and 6 grams of 0.1MK / g carbon black were suspended in 100 mL (200 mL for 6 gram batches) of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassed). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After 15 minutes of bubbling with CO, 15 mL (per gram of Cu / C) of 0.1MK / g carbon black was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. PtCu containing 26.4 wt% Pt and 25.9 wt% Cu 3 The / C electrocatalyst was finally recovered.
[0111] Example 10: In a two-neck round-bottom flask, a Cu / C mixture containing 33 wt% Cu (C: BET surface area 1000 m 21–3 grams of 0.1MK / g carbon black were suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After 15 min of bubbling with CO, 15 mL (per gram of Cu / C) of 0.1MK / g carbon black was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. PtCu containing 25.5 wt% Pt and 26 wt% Cu 3 The / C electrocatalyst was finally recovered.
[0112] Example 11: In a two-neck round-bottom flask, a Cu / C mixture containing 33 wt% Cu (C: BET surface area 1400 m 2 One gram of 0.1MK / g carbon black was suspended in 100 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then purged with CO for 15 minutes while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 minutes, 15 mL of 0.1MK was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. PtCu containing 26 wt% Pt and 25.6 wt% Cu was added. 3 The / C electrocatalyst was finally recovered.
[0113] Table 1. The same type of carbon support (BET surface area 250 m) after 200 cycles of in situ EA (0.05–1.2 V vs. RHE, 300 mV / s) 2 / g of carbon black) but with different metal loadings (Pt+Cu). 3 TF-RDE evaluation of / C electrode catalysts. TIFF0007601853000002.tif21575
[0114] Table 2. The results of the same type of carbon support (BET surface area 250 m) after 200 cycles of in situ EA (0.05–1.2 V vs. RHE, 300 mV / s). 2 / g of carbon black) but with different Pt:Cu chemical compositions. 3 TF-RDE evaluation of / C electrode catalysts. TIFF0007601853000003.tif21575
[0115] Table 3. Four PtCu nanoparticles supported on different types of commercial carbon supports after 200 cycles of in situ EA (0.05–1.2 V vs. RHE, 300 mV / s). 3 TF-RDE evaluation of / C electrode catalysts. TIFF0007601853000004.tif22275
[0116] Figure 4 shows the XRD spectra of products with different total metal loadings (Pt+Cu) by using Cu / C precursors with different Cu loadings on the same carbon support (Examples 1, 2, 4 and 8). This series of analogs (see Table 1) and Figure 5 show the XRD spectra of PtCu after in situ EA. 3 The CO stripping CV, ORR polarization curves, and calculated Tafel plots of the Pt / C electrocatalysts (Examples 1, 2, 4, and 8) are shown. CO The area corresponding to the CO stripping area (surface area of platinum normalized by the mass of platinum) and thus the MA is reduced, but the area corresponding to the CO stripping area (surface area of platinum per mass of catalyst) actually increases. Furthermore, this series of analogues shows the flexibility in designing different total metal loadings (Pt+M), which is necessary when high metal loadings are required and at the same time ECSA CO At least 40m 2 / g PtThis is of great importance for applications in PEMFCs beyond 1000 sq.m. All four electrocatalysts significantly outperform the state-of-the-art Pt / C electrocatalyst in terms of SA and MA.
[0117] Figure 6 shows the results of the experiment in which a Cu / C precursor with a fixed Cu content was treated with different amounts of K. 2 PtCl 4 XRD spectra of precursor-doped products with different Pt:Cu chemical compositions are shown (Examples 4-7). As a reference, a commercial Pt-Cu / C electrocatalyst (PK catalyst) was analyzed, which showed a very similar XRD pattern to the PtCu / C electrocatalyst from Example 5. This series of analogues demonstrates that the "double passivation" GD method can be used to produce PtM 3 It shows that the ECSA is not limited by the crystal structure but rather by the amount of sacrificial metal (M). Figure 7 shows the CO stripping CV, ORR polarization curves, and calculated Tafel plots of Pt-Cu / C electrocatalysts after in situ EA (Examples 4-7). The results well show that more Pt in the chemical composition exhibits lower SA for ORR at 0.9 V vs. RHE in the order of Example 4 > Example 5 > Example 6 > Example 7 (see Table 2 and Figure 7). Nevertheless, all the presented Pt-Cu / C electrocatalysts exhibit improved SA in contrast to the state-of-the-art Pt / C electrocatalysts. All the Pt-Cu / C electrocatalysts have sufficient ECSA. CO (40m 2 / g Pt (super high), thus outperforming the state-of-the-art Pt / C electrocatalyst in terms of MA.
[0118] FIG. 8 shows the XRD spectra of products with similar total metal loading (Pt+Cu) and Pt:Cu chemical composition but different carbon supports. In these examples, the BET is between 250 and 1400 m. 2 / g of carbon support was used (Examples 8-11). This series of analogs in Figure 9 (see Table 3) shows the corresponding PtCu 3 The CO stripping CV, ORR polarization curves, and calculated Tafel plots of the carbon support / C electrode catalysts (Examples 8 to 11) are shown.CO A trend towards increased CO stripping area was observed. Thus, according to these examples, the higher the BET of the carbon support, the better the dispersion of the precious metal alloy nanoparticles (Examples 8-11) with similar total metal loading (Pt+Cu). This is because the ECSA could be achieved without sacrificing the total metal loading (Pt+Cu) as in the case of Examples 1, 2, 4 and 8. CO and is an excellent method to increase the CO stripping area. All four electrocatalysts also significantly outperform the state-of-the-art Pt / C electrocatalyst in terms of SA and MA.
[0119] Although spontaneous GD reactions occurred with or without CO during the addition of the Pt salt precursor, there were significant differences in the resulting PtCu+CuO / C composites (Figure 10), see Example 3. As seen from the overlapping peaks in Figure 10a, carrying out the reaction in the presence of CO does not affect the resulting CuO phase (35.7°(-111) and 38.9°(111)2θ). On the other hand, there is a subtle but significant difference in the most intense peaks corresponding to the PtCu phase (41.2°(111) and 47.9°(200)2θ). The differences obtained are a direct consequence of the strong Pt-CO interaction, where CO acts as a very efficient capping agent that prevents excessive aggregation and growth of the nanoparticles formed by passivating the Pt surface. After subsequent thermal annealing of both analogues (Figure 10b), Pm3m PtCu 3 The differences in the XRD spectra obtained for the phases (24.1°(100), 34.3°(110), 42.4°(111) and 49.3°(200)2θ) are more evident, indicating that the PtCu 3The crystallite size is much smaller in the PtCu+CuO / C-CO case. To further confirm the differences observed in the XRD spectra in Fig. 10a) and b), additional ex situ TEM analysis was performed (Fig. 10c-f). Before thermal annealing in the case of PtCu+CuO / C analogue (Fig. 10c), large aggregates of small PtCu nanocrystallites are observed. The observed small but aggregated PtCu nanocrystallites are consistent with the XRD spectrum, where the peaks corresponding to the PtCu phase are still rather broad. In contrast, in the case of PtCu+CuO / C-CO analogue (Fig. 10d), we instead observe an almost complete dispersion of the PtCu nanoparticles. After subsequent thermal annealing, the poorly dispersed aggregated PtCu nanocrystallites sinter into large spherical particles (Fig. 10e). In contrast, the optimally dispersed PtCu particles remain small and well dispersed after heat treatment (Fig. 10f). This comparison reveals the important role of the initial dispersion properties (absence of severe agglomeration) in preventing excessive particle growth upon heat treatment, even at high temperatures of 800 °C. Such properties of the initial dispersion are essentially only possible in the case of double passivation (two of the three paths of electrons are blocked), whereas the absence of a second passivation (only one of the three paths of electrons is blocked) leads to severe agglomeration, as shown in this example. The difference in Pt surface area is due to the fact that PtCu 3 / C (Example 3) and PtCu 3 0.1M HClO by comparing both analogs of / C-CO (Example 2) 4 This can be further evaluated by a "CO stripping" experiment in ECSA based on the "CO stripping" experiment. CO was measured after 200 cycles of electrochemical cycling activation (0.05–1.2 V vs. RHE, 300 mV / s), Fig. 10g) and h). 3 The / C-CO analogue had a greater than 2-fold increase in ECSA. CO By having CO gas in the cytosol, it performs much better than analogs synthesized without CO gas.
[0120] Example 12: In a two-necked round-bottom flask, Ni / C containing 14.1 wt% Ni (C: BET surface area 250 m 2 One gram of carbon black (1000 g / g) was suspended in 100 mL of 0.0001 M KOH (Merck). The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 min, 5 mL of 0.1 MKOH was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. 3 The / C electrocatalyst was finally recovered.
[0121] Example 13: In a two-necked round-bottom flask, Ni / C containing 14.1 wt% Ni (C: BET surface area 250 m 2 One gram of carbon black (1000 g / g) was suspended in 100 mL of 0.0001 M KOH (Merck). The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with Ar for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with Ar for 15 min, 5 mL of 0.1 MKOH was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with Ar. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. 3 Ni+PtNi 3 The +Ni / C electrocatalyst was finally recovered.
[0122] Example 14: In a two-necked round-bottom flask, a Co / C mixture containing 14.1 wt% Co (C: BET surface area 250 m 2One gram of carbon black (1000 g / g) was suspended in 100 mL of 0.001 M KOH (Merck). The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO for 15 min, 5 mL of 0.1 MKOH was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. 3 The / C electrocatalyst was finally recovered.
[0123] Example 15: In a two-necked round-bottom flask, a Co / C mixture containing 14.1 wt% Co (C: BET surface area 250 m 2 One gram of carbon black (1000 g / g) was suspended in 100 mL of 0.001 M KOH (Merck). The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with Ar for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with Ar for 15 min, 5 mL of 0.1MK was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with Ar. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. 3 Co+PtCo 3 The +Co / C electrocatalyst was finally recovered.
[0124] Figures 11a) and b) show the XRD patterns of the double passivation GD synthesis method using Ni / C precursor in the Pt-Ni system (Examples 12 and 13). Similar to the Pt-Cu system described above, the GD reaction occurred with or without CO during the addition of the Pt salt precursor, with significant differences in the resulting Pt+Ni / C composites. As seen in Figure 11a), the most intense peaks of the Pt phase (39.8°(111) and 46.2°(200)2θ) were broadened by GD in the presence of CO, thus representing smaller nanocrystallites. As in the case of the Pt-Cu system, there was no noticeable difference in the most intense peaks of the less noble metal (Ni) phase (44.3°(111) and 51.7°(200)2θ). Moreover, after thermal annealing (Figure 11b), the sample with CO contained PtNi 3 The sample without CO showed only PtNi 3 Besides the crystalline phases (42.4°(111) and 49.3°(200)2θ), there are still Pt 3 The presence of Ni (40.4°(111) and 51.7°(200)2θ) and Ni (44.3°(111) and 46.8°(200)2θ) crystalline phases is also shown. The heterogeneity of the crystalline phases in the case of the sample synthesized without the presence of CO during the GD synthesis step is most likely a result of poorer dispersion of the Pt nanoparticles due to the absence of capping CO gas.
[0125] Figure 11c) and d) show the XRD patterns of the double passivation GD synthesis method using Co / C precursor in the Pt-Co system (Examples 14 and 15). Similar to the Pt-Cu system described above, the GD reaction occurred regardless of the presence or absence of CO when the Pt salt precursor was added, and the resulting Pt+Co 3 O 4 There was a significant difference in the Pt / C composites. As can be seen in Fig. 11c, the peaks of the Pt phase (40.0°(111) and 46.5°(200)2θ) are broadened by GD in the presence of CO, thus representing smaller nanocrystallites. As in the case of the Pt-Cu system, the peaks of the less noble metal (Co 3 O 4) phase (19°(111), 31.3°(220), 36.8°(311), 44.8°(400) and 55.6°(422) 2θ). Furthermore, after thermal annealing (Figure 11d), the sample with CO showed no significant difference in the most intense peaks of PtCo 3 The sample without CO showed only Pt crystalline phases (42.6°(111) and 49.6°(200)2θ) present, along with some remaining Co (44.2°(111) and 51.5°(200)2θ) crystalline phases. 3 Co (24.1(100), 33.3(110), 41.0°(111) and 49.6°(200)2θ) and PtCo 3 (42.2°(111) and 49.1°(200)2θ) crystalline phases. The heterogeneity of the crystalline phase in the case of the sample synthesized without the presence of CO during the GD synthesis process is most likely a result of poorer dispersion of the Pt nanoparticles due to the absence of capping CO gas.
[0126] It has been shown that the dual passivation GD method of the present invention provides high flexibility in the design of the final product. The method allows for variations in the chemical composition of precious metal:M, the total metal loading of M on the carbon support, and the carbon support itself. Furthermore, the dual passivation GD method has been shown to provide well-dispersed nanoparticles on the carbon support, which provide high mass activity when used as an electrocatalyst material. In particular, the carbon-supported platinum alloy nanoparticle catalysts prepared according to the present invention have been shown to have very high SA (specific activity) and MA (mass activity) for ORR (oxygen reduction reaction) due to the small particle size and alloying of platinum and M.
[0127] Example 16: The CuO+Cu reduced graphene oxide composite was synthesized in two steps. In the first step, graphene oxide was prepared from graphite (TIMREX KS44) using a modified Hummers method ("Improved synthesis of Graphene Oxide", Marcanto, DC et al, ACS Nano 2010, 4, 8, 4806-4814). In the second step, a suspension of as-synthesized graphene oxide with copper(II) acetate monohydrate (Merck) and Milli-Q water was pumped into a pulsed combustion / thermoacoustic reactor where the copper(II) acetate monohydrate and graphene oxide were thermally reduced under an inert acetylene atmosphere. A black composite of CuO+Cu reduced graphene oxide was collected. For the purpose of the double passivation method, 200 mg of CuO+Cu reduced graphene oxide composite containing 38 wt% Cu was suspended in 20 mL of ultrapure water in a two-neck round-bottom flask. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO for 15 min while being stirred with a magnetic stirrer at 900 rpm to achieve saturation. After 15 min of CO bubbling, 1.5 mL (per 100 milligrams of CuO+Cu reduced graphene oxide) of 0.1 MKCl was added by a syringe pump (WPI sp100i, flow rate 160 mL / h) while the reaction mixture was continuously purged with CO. 2 PtCl 4 (Apollo Scientific) was added. All other conditions were the same as in Example 1. After thermal annealing, PtCu+PtCu 3 The reduced graphene oxide electrocatalyst was finally recovered.
[0128] Figure 12a) shows the XRD pattern of CuO+Cu composite on reduced graphene oxide prepared in a thermoacoustic reactor (Example 16). As with the Pt-Cu system on carbon black described above, the GD reaction occurred via the same double passivation mechanism. Figure 12b) shows the XRD pattern of PtCu+CuO composite on reduced graphene oxide (as synthesized) after synthesis with double passivated GD (Example 16). As can be seen in Figure 12b), similar to the synthesis on carbon black, there are broad PtCu phase peaks (41.2°(111) and 47.9°(200)2θ) in addition to the sharper CuO phase peaks (35.7°(-111) and 38.9°(111)2θ). After subsequent thermal annealing, the ratio of Pt to Cu results in Pm3m PtCu 3 Both the R-3m phase (24.1°(100), 34.3°(110), 42.4°(111) and 49.3°(200) 2θ) and the R-3m phase (20.4°(021), 39.2°(205), 41°(006) and 47.9°(404) 2θ) are observed. The broadness of the main peak in the XRD pattern indicates a small crystallite size (Example 16).
[0129] It has been shown that the double passivation GD method of the present invention provides high flexibility in the choice of support material for the use of reduced graphene oxide based composites. Moreover, according to Example 16, the present invention also shows the possibility of using ex-situ partially passivated M / S precursors.
[0130] Example 17: TiO x N y The following procedure was used to obtain metallic Cu on the substrate. In the first step, TiO x N y NH 3 Under air current (50cm 3 min -1 ) at 730°C for 12 hours (heating and cooling rates were both 5°C min -1 (TiO 2(Degussa P25) by thermal annealing. In the second step, 180 mg of CuBr 2 was dissolved in 0.4 mL of Milli-Q water. 2 The solution was added with the TiO obtained in the first step. x N y 200 mg of substrate was added. The mixture was then dried at 50° C. for 30 min. The dried CuBr 2 Impregnated TiO x N y The powder was then treated with NH 3 (50cm 3 min -1 The sample was then thermally annealed again at 730 °C under a stream of 10000 kcal / kg (5 h, heating rate 2 °C min -1 , cooling rate 3℃ min -1 In the final step, a double passivation with GD was used to remove TiO x N y Pt was deposited on the substrate. For the double passivation GD process, TiO x N y 75 mg of the above Cu (approximately 20 wt% Cu) was suspended in 20 mL of ultrapure water. This suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO gas for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO gas for 15 min, 0.688 mL of 0.1MK was added to the reaction mixture by a syringe pump (WPI sp100i, flow rate 160 mL / h) while continuously purging with CO gas. 2 PtCl 4 (Apollo scientific) was added. After all the Pt precursor was added to the reaction mixture, the suspension was filtered and redispersed in fresh ultrapure water. After mixing for 15 minutes, the suspension was filtered again and the process was repeated a total of three times. After the final filtration, the resulting PtCu+CuO / TiO x N y The composite was left to dry at 50° C. overnight.
[0131] FIG. 13 shows 1) a protected TiO x N ySupport (Example 17), 2) Cu+TiO before synthesis using the double passivation GD method x N y Composite (Example 17), and 3) PtCu+CuO / TiO after synthesis using the double passivation GD method. x N y The XRD pattern of the composite (Example 17) is shown. As in the Pt-Cu system on carbon black described above, the GD reaction occurred via the same double passivation mechanism. As seen in FIG. 13, after synthesis using the double passivation GD method, similar to the synthesis on carbon black, the pure CuFm-3m phase (43.3°(111) and 50.4°(200)2θ) disappears, and the broad PtCu phase peaks (41.2°(111) and 47.9°(200)2θ) and CuO phase peaks (35.7°(-111) and 38.9°(111)2θ) appear. TiO x N y The crystalline phases (37°(111) and 43°(200)2θ) remain intact throughout the synthesis (Example 17).
[0132] The dual passivation GD method of the present invention uses conductive ceramics (TiO x N y It has been shown that the use of .
[0133] Example 18: Cu+Cu on carbon black 2 The O+CuO complex was synthesized in a single step. The BET surface area was 800 m 2 A suspension of 1000g / g of carbon black, copper(II) acetate monohydrate (Merck) and Milli-Q water was pumped into a pulsed combustion / thermoacoustic reactor where copper(II) acetate monohydrate was thermally reduced on the carbon black under an inert acetylene atmosphere. Cu+Cu 2 The black composite of O+CuO carbon black was collected. Cu+CuO, which contained 41 wt% Cu, was collected in a two-neck round-bottom flask. 2100 mg of O+CuO carbon black was suspended in 30 mL of ultrapure water. This suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 minutes (degassing). The suspension was then stirred with a magnetic stirrer at 900 rpm for 15 minutes in H 2 Saturation was achieved by purging with H 2 After bubbling gas for 15 min, the reaction mixture was cooled to 10°C. 2 17.5 mL of 0.01 M NaCl was dispensed into the syringe using a syringe pump (WPI sp100i, flow rate 10 mL / h) while being continuously purged with gas. 2 PdCl 4 Added 0.01M Na 2 PdCl 4 The solution is non-aqueous PdCl 2 (Sigma Aldrich) and a three-fold molar excess of NaCl. After all the Pd precursor was added to the reaction mixture, the suspension was filtered and redispersed in fresh ultrapure water. After mixing for 15 min, the suspension was filtered again and the process was repeated a total of three times. After the final filtration, the resulting Pd+Cu 2 The O+CuO carbon black composite was left to dry overnight at 50°C.
[0134] Example 19: Cu+Cu on carbon black 2 The O+CuO complex was synthesized in a single step. The BET surface area was 800 m 2 A suspension of 1000g / g of carbon black, copper(II) acetate monohydrate (Merck) and Milli-Q water was pumped into a pulsed combustion / thermoacoustic reactor where copper(II) acetate monohydrate was thermally reduced on the carbon black under an inert acetylene atmosphere. Cu+Cu 2 The black composite of O+CuO carbon black was collected. Cu+CuO, which contained 41 wt% Cu, was collected in a two-neck round-bottom flask. 2100 mg of O+CuO carbon black was suspended in 30 mL of ultrapure water. The suspension was placed in an ultrasonic bath (ultrasonic bath Iskra Sonis 4) for 3 min (degassing). The suspension was then purged with CO gas for 15 min while stirring with a magnetic stirrer at 900 rpm to achieve saturation. After bubbling with CO gas for 15 min, 17.5 mL of 0.01 M Na was added to the reaction mixture by a syringe pump (WPI sp100i, flow rate 10 mL / h) while continuously purging with CO gas. 2 PdCl 4 Added 0.01M Na 2 PdCl 4 The solution is non-aqueous PdCl 2 (Sigma Aldrich) and a three-fold molar excess of NaCl. After all the Pd precursor was added to the reaction mixture, the suspension was filtered and redispersed in fresh ultrapure water. After mixing for 15 min, the suspension was filtered again and the process was repeated a total of three times. After the final filtration, the resulting Pd+Cu 2 The O+CuO / carbon black composite was left to dry at 50° C. overnight.
[0135] Figure 14 shows 1) Cu+Cu on carbon black 2 1) H+CuO complex (Examples 18 and 19), 2) H using the double passivation GD method 2 Pd+Cu on as-synthesized carbon black in the presence of gas 2 O+CuO composite (Example 18), and 3) Pd+Cu on as-synthesized carbon black in the presence of CO gas using the double passivation GD method. 2 14 shows the XRD pattern of the O+CuO composite (Example 19). As in the system on carbon black with Pt as the noble metal described above, the GD reaction occurred via the same dual passivation mechanism. Thus, in cases 2 and 3, 2 As-synthesized Pd+Cu on carbon black support using either CO gas (Example 18) or CO gas (Example 19). 2A comparison of the obtained XRD patterns of the O+CuO composites is shown. Similar to the synthesis with Pt as the noble metal, there is a sharper CuO phase peak (35.7°(-111) and 38.9°(111)2θ) and Cu 2 In addition to the O phase peaks (36.4°(111) and 42.3°(200) 2θ), broad noble metal (Pd) phase peaks (40.2°(111) and 46.8°(200) 2θ) are present.
[0136] It has been shown that the dual passivation GD method of the present invention offers great flexibility in the use of other noble metals and adsorbed gases. Furthermore, similar to Example 16, Examples 18 and 19 show that the present invention also offers the possibility of using partially ex-situ passivated M / S precursors.
[0137] While various embodiments of the present invention have been described, it will be apparent to one of ordinary skill in the art that other embodiments incorporating its concepts may be used. These and other examples of the invention illustrated above and in the accompanying drawings are intended to be illustrative only, with the actual scope of the invention being defined by the claims that follow.
Claims
1. A method for forming supported precious metal nanoparticles and / or precious metal-M alloy nanoparticle composites, wherein M is a less noble metal that is galvanically substituted to precipitate the precious metal, the method comprising: (a) providing an M / S precursor material having metal particles M on electrically conductive support particles S, where M is one or more metals having a lower standard electrode potential than the noble metal; (b) suspending the M / S precursor material in a liquid medium and forming a passivated MO y forming a liquid medium having a pH at which an in situ passivating oxide is thermodynamically formed at least on surfaces of the metal M particles exposed to the liquid medium, and y is greater than 0 and up to the stoichiometric M oxide value; (c) introducing an adsorption gas capable of selectively adsorbing the precious metal to be deposited into the MO y 3. providing a .OMEGA. / S suspension; (d) The MO y adding a precious metal precursor to the M / S suspension, thereby precipitating crystalline precious metal nanoparticles and / or crystalline precious metal-M alloy nanoparticles as a reaction product on the support particles by a galvanic replacement reaction; and (e) separating and washing the as-synthesized reaction product. A method comprising:
2. 2. The method of claim 1, wherein the metal M of the M / S precursor in step (a) is at least partially oxidized to form an ex situ passivated M+MO / S precursor.
3. The liquid medium may be water, an alcohol having 1 to 7 carbon atoms, CH 4 O to C 7 H 16 3. The method of claim 1, wherein the alcohol is 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30
4. 4. The method of any one of claims 1 to 3, wherein the pH of the liquid medium is adjusted before, during and / or after suspension of the M / S precursor material and / or the at least partially ex-situ passivated M+MO / S precursor.
5. The passivated metal y 5. The method according to claim 1, wherein the / S suspension is saturated with the adsorption gas prior to the addition of the precious metal precursor.
6. 6. The method of claim 5, wherein the adsorbed gas is provided from an external source and / or is formed at least partially in situ in the suspension.
7. 7. The method of claim 5 or 6, wherein the addition of the adsorption gas is continued during the addition of the precious metal precursor.
8. The method according to any one of claims 1 to 7, wherein the precious metal precursor is a salt or the corresponding acid of said salt that is soluble in the liquid medium.
9. 9. The method of claim 1, wherein the noble metal is Pt, Ir, Rh, Pd, or Au.
10. The adsorbed gas is carbon monoxide (CO), hydrogen (H 2 ), methanethiol (MeHS), or hydrogen sulfide (H 2 The method according to any one of claims 1 to 9, wherein the scavenger is selected from the group consisting of scavenger, scavenger and scavenger.
11. The method of any one of claims 1 to 10, wherein the noble metal is Pt or Pd and the adsorbed gas is CO.
12. The noble metal is Pd and the adsorption gas is H 2 The method according to any one of claims 1 to 10, wherein
13. 13. The method of any one of claims 1 to 12, wherein the less noble metal M is selected from Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Sn, Mo, W, Zn, Y, Gd, Pd, or mixtures thereof.
14. 14. The method according to claim 1, wherein the support particles are an electrically conductive material selected from a carbon material, a ceramic material, or a composite material, the electrical conductivity of which is greater than the electrical conductivity of the passivating oxide formed.
15. 15. The method of claim 14, wherein the carbon material is a conductive carbon particle selected from carbon black, carbon nanotubes (CNTs), graphite or graphene, or derivatives thereof.
16. The ceramic material is antimony tin oxide (ATO), fluorine doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x N y 15. The method of claim 14, wherein the ceramic particles are selected from the group consisting of:
17. 17. The method of any one of claims 1 to 16, wherein the washing in step (e) comprises redispersing the as-synthesized reaction product in a fresh liquid medium and filtering at least once.
18. 20. The method of claim 17, wherein the washed and filtered as-synthesized reaction product is dried.
19. The method of any one of claims 1 to 18, further comprising a step (f) of thermal annealing the as-synthesized product.
20. 20. The method of claim 19, wherein the thermal annealing step (f) is carried out at a temperature between 450 and 1200° C. under an inert, oxygen-free, and / or reducing atmosphere.
21. MO oxide on a support material, y being greater than 0 and up to the stoichiometric M oxide value. y 1. A composite material comprising precious metal and / or precious metal-M alloy nanoparticles combined with a particle, M is a less noble metal galvanically substituted by the noble metal in a cationic state, and the composite material is an as-synthesized reaction product comprising highly dispersed noble metal nanoparticles and / or noble metal-M nanoparticles on the support material; the noble metal nanoparticles and / or noble metal-M nanoparticles and the MO y particles are distributed separately on the support material; Composite material.
22. 1. A composite material comprising precious metal nanoparticles and / or precious metal-M alloy nanoparticles on a support material, M is a less noble metal galvanically substituted by the noble metal in a cationic state, and the composite material is an annealed reaction product comprising highly dispersed noble metal nanoparticles and / or noble metal-M nanoparticles on the support material; the noble metal nanoparticles and / or noble metal-M nanoparticles are alloyed with element M; Composite material.
23. 23. The composite material of claim 21 or 22, wherein the noble metal is Pt, Ir, Rh, Pd, or Au.
24. 24. The composite material of any one of claims 21 to 23, wherein the less noble metal M is Cu, Ni, Co, Fe, Ag, Cr, Ti, Pb, Sn, Mo, W, Zn, Y, Gd, Pd, or a mixture thereof.
25. 25. The composite material of any one of claims 21 to 24, wherein the support material is an electrically conductive material selected from a carbon material, a ceramic material, or a composite material.
26. 26. The composite material of claim 25, wherein the carbon material is a conductive carbon particle selected from carbon black, carbon nanotubes (CNTs), graphite or graphene, or derivatives thereof.
27. The ceramic material is antimony tin oxide (ATO), fluorine doped tin oxide (FTO), indium tin oxide (ITO), or titanium oxynitride (TiO x N y 26. The composite material of claim 25, wherein the ceramic particles are selected from:
28. 23. The composite material of claim 21 or 22, wherein the precious metal is Pt, the M is one or more of Cu, Ni, or Co, and the support material is carbon black.
29. Use of the composite material according to any one of claims 21 to 28 as an electrocatalyst in an electrochemical energy conversion device.
30. 30. The use of a composite material according to claim 29, wherein said composite material has been treated by a catalytic activation treatment.
31. 31. Use of the composite material according to claim 29 or 30, wherein the catalyst is a carbon supported Pt-M alloy nanoparticle electrocatalyst in a PEM fuel cell.
Citation Information
Patent Citations
Method for producing platinum catalyst and fuel cell using the same
JP2017029967A
Graphite Particle-Supported Pt-Shell / Ni-Core Nanoparticle Electrocatalyst for Oxygen Reduction Reaction
US20120208108A1
Platinum nickel nanowires as oxygen reducing electrocatalysts and methods of making the same
US20160126562A1
Method for Manufacturing Platinum Catalyst, and Fuel Cell Including the Same
US20180047993A1
